Access to a Labile Monomeric Magnesium Radical by Ball-Milling - Jedrzkiewicz, Dawid; Mai, Jonathan; Langer, Jens; Mathe, Zachary; Patel, Neha; DeBeer, Serena; Harder, Sjoerd (Angewandte Chemie International Edition, 2022)
In order to isolate a monometallic Mg radical, the precursor (Am)MgI⋅(CAAC) (1) was prepared (Am=tBuC(N-DIPP)2, DIPP=2,6-diisopropylphenyl, CAAC=cyclic (alkyl)(amino)carbene). Reduction of a solution of 1 in toluene with the reducing agent K/KI led to formation of a deep purple complex that rapidly decomposed. Ball-milling of 1 with K/KI gave the low-valent MgI complex (Am)Mg⋅(CAAC) (2) which after rapid extraction with pentane and crystallization was isolated in 15 % yield. Although a benzene solution of 2 decomposes rapidly to give Mg(Am)2 (3) and unidentified products, the radical is stable in the solid state. Its crystal structure shows planar trigonal coordination at Mg. The extremely short Mg−C distance of 2.056(2) Å indicates strong Mg−CAAC bonding. Calculations and EPR measurements show that most of the spin density is in a π* orbital located at the C−N bond in CAAC, leading to significant C−N bond elongation. This is supported by calculated NPA charges in 2: Mg +1.73, CAAC −0.82. Similar metal-to-CAAC charge transfer was calculated for M0(CAAC)2 and [MI(CAAC)2+] (M=Be, Mg, Ca) complexes in which the metal charges range from +1.50 to +1.70. Although the spin density of the radical is mainly located at the CAAC ligand, complex 2 reacts as a low-valent MgI complex: reaction with a I2 solution in toluene gave (Am)MgI⋅(CAAC) (1) as the major product.
CRIS-Team Scopus Importer:2022-02-25
Keywords: DFT Calculations; EPRSpectroscopy; Low-Valent Complexes; Magnesium; Radicals

Alkali metal influences in aluminyl complexes - Grams, Samuel; Mai, Jonathan; Langer, Jens; Harder, Sjoerd (Dalton Transactions, 2022)
The previously reported potassium aluminyl complex [(BDI-H)Al−K+]2 was converted in Li+ or Na+ salts by a salt metathesis reaction with Li(BPh4) or Na(BPh4), respectively; BDI-H = dianionic [(DIPP)N-C(Me) 00000000 00000000 00000000 00000000 11111111 00000000 11111111 00000000 00000000 00000000 C(H)-C( CH2)-N(DIPP)2−] and DIPP = 2,6-diisopropylphenyl. The Rb and Cs aluminyl complexes were obtained by reaction of (BDI)Al with RbC8 or CsC8; BDI = HC[C(Me)N(DIPP)]2. Crystal structures of two monomers, (BDI-H)Al−Li+·(Et2O)2 and (BDI-H)Al−Na+·(Et2O)(TMEDA), and four dimers [(BDI-H)Al−M+]2 (M = Li, Na, Rb, Cs) are discussed. Lewis base-free dimers [(BDI-H)Al−M+]2 crystallize either as slipped dimers (Li+, Na+) in which each Al center features only one Al-M contact or as a symmetric dimer (K+, Rb+, Cs+) in which the cation bridges both Al centers. The dimer with the largest cation (Cs+) shows Cs⋯CH2 C interactions between dimers, resulting in a coordination polymer. AIM and charge analysis reveal highly ionic Al-M bonds with strong polarization of the Al lone-pair towards the smaller cation Li+ and Na+. The Al-M bonds become weaker from Li to Cs. Calculated dimerization energies suggest that in apolar solvents only complexes with the heavier metals Rb and Cs may be in a monomer-dimer equilibrium. This is confirmed by DOSY measurements in benzene. Dimeric aluminyl complexes with heavier alkali metals (K-Cs) react with benzene to give a double C-H activation in para-positions.
CRIS-Team Scopus Importer:2022-08-12

Alkaline Earth Metal Aluminates as Catalysts for Imine Hydrogenation - Elsen, Holger; Langer, Jens; Wiesinger, Michael; Harder, Sjoerd (Organometallics, 2020)
Alkaline earth (Ae) metal complexes with the alanate anion AlH4 - have been prepared by salt metathesis between NaAlH4 and AeCl2 in THF and could be isolated as Mg(AlH4)2·(THF)4, Ca(AlH4)2·(THF)4, and Sr(AlH4)2·(THF)5. The previously reported crystal structure of the Mg alanate complex shows bonding of AlH4 - with one bridging hydride, H3Al-(μ-H)-Mg, while the Ca and Sr alanates show a combination of H3Al-(μ-H)-Ae and H2Al-(μ-H)2-Ae bridging. The heteroleptic β-diketiminate complexes (DIPPBDI)Mg(AlH4)·THF and (DIPPBDI)Ca(AlH4)·(THF)2 have been prepared by reaction of the corresponding Ae hydride complexes with AlH3·(THF)2 [DIPPBDI = DIPP-NC(Me)C(H)C(Me)N-DIPP, where DIPP = 2,6-diisopropylphenyl]. Crystal structures show H2Al-(μ-H)2-Ae bridging. The Ca complex decomposes at room temperature by reduction of the β-diketiminate anion. Density functional theory calculations (B3PW91/def2tzvpp) show that the formation of Ae(AlH4)2 from AeH2 and AlH3 is exothermic by ΔH (kilocalories per mole): Be, -68.8; Mg, -66.1; Ca, -95.4; Sr, -100.9; Ba, -112.3. Calculations of NPA charges on LiAlH4 and the Ae alanate complexes (Ae = Mg, Ca, or Sr) show that these are highly ionic salts in which the charge on AlH4 - of approximately -0.95 is hardly dependent on the countercation. Compared to LiAlH4, the Ae alanates are very efficient catalysts for imine hydrogenation, clearly extending the substrate scope. In addition to aldimines RC(H)═NR′ (R/R′ = Ph/tBu, tBu/tBu, nPr/tBu, or Ph/Ph), ketimine PhC(Me)═NtBu could be reduced. The salt [Bu4N+][AlH4 -] is catalytically not active, which shows that the s-block metal is crucial. The highest activities were found for the heterobimetallic Ca and Sr alanates.
CRIS-Team Scopus Importer:2020-06-09

Alkaline Earth Metal Imido Complexes with Doubly Deprotonated Amidine and β-Diketimine Ligands - Martin, Johannes; Langer, Jens; Elsen, Holger; Harder, Sjoerd (European Journal of Inorganic Chemistry, 2020)
Double deprotonation of the amidine DIPP-N=C(tBu)-NH2 or β-diketimine DIPP-N=C(Me)-C(H)=C(Me)-NH2 (DIPP = 2,6-diisopropylphenyl) with strong benzylcalcium or strontium bases gave metal imido complexes with the anions DIPP-N=C(tBu)-N2– (Am2–) and DIPP-N=C(Me)-C(H)=C(Me)-N2– (BDI2–) which crystallized as tetrameric complexes with typical Ca4N4 or Sr4N4 cubane frameworks. Crystal structures of [(Am)Ca·THF]4, [(BDI)Ca·THF]4 and the first Sr imido complex [(Am)Sr·THF]4 are presented. Calculated geometries of [(Am)Ca·THF]4 and [(BDI)Ca·THF]4 (B3PW91/6-311++G**) are in good agreement with the crystal structures. Also complexes with monoanionic ligands (Am-H)– and (BDI-H)– are reported. Charge delocalization in the ligand backbone is discussed. Ligand–metal bonds are calculated to be circa 90 % ionic; the NPA charges on Ca is circa +1.8. The negative charge on the ligand is delocalized over the ligand backbone but there is still considerable electron density on the terminal N (–1.4). Despite this high negative charge, the reactivity of these complexes is generally low due to the strongly bound cubane core. Reaction of [(Am)Ca·THF]4 with phenyl cyanide gave the [(Am)Ca·PhCN]4, clearly demonstrating its low reactivity. Attempts to break the tetrameric cluster in smaller aggregates by addition of 18-crown-6 led to protonation and isolation of (Am-H)2Ca·(18-crown-6). Reaction of [(Am)Ca·THF]4 with iPrN=C=NiPr gave after addition a complex with a unique amido-guanidinate ligand.
CRIS-Team Scopus Importer:2020-10-02
Keywords: Alkaline earth metals; Amidinates; Density functional calculations; Imido ligands; β-Diketiminates

Alkaline-Earth Metal Mediated Benzene-to-Biphenyl Coupling - Mai, Jonathan; Morasch, Michael; Jedrzkiewicz, Dawid; Langer, Jens; Rösch, Bastian; Harder, Sjoerd (Angewandte Chemie International Edition, 2022)
Complex [(DIPePBDI)Ca]2(C6H6), with a C6H62− dianion bridging two Ca2+ ions, reacts with benzene to yield [(DIPePBDI)Ca]2(biphenyl) with a bridging biphenyl2− dianion (DIPePBDI=HC[C(Me)N-DIPeP]2; DIPeP=2,6-CH(Et)2-phenyl). The biphenyl complex was also prepared by reacting [(DIPePBDI)Ca]2(C6H6) with biphenyl or by reduction of [(DIPePBDI)CaI]2 with KC8 in presence of biphenyl. Benzene-benzene coupling was also observed when the deep purple product of ball-milling [(DIPPBDI)CaI(THF)]2 with K/KI was extracted with benzene (DIPP=2,6-CH(Me)2-phenyl) giving crystalline [(DIPPBDI)Ca(THF)]2(biphenyl) (52 % yield). Reduction of [(DIPePBDI)SrI]2 with KC8 gave highly labile [(DIPePBDI)Sr]2(C6H6) as a black powder (61 % yield) which reacts rapidly and selectively with benzene to [(DIPePBDI)Sr]2(biphenyl). DFT calculations show that the most likely route for biphenyl formation is a pathway in which the C6H62− dianion attacks neutral benzene. This is facilitated by metal-benzene coordination.
CRIS-Team Scopus Importer:2022-12-23
Keywords: Alkaline-Earth Metal; Cross-Coupling; DFT Calculations; Low-Valent; Mechanochemistry

Application of a Stable and Soluble Dibenzylbarium Reagent in the Synthesis of a Barium Imido Cluster - Rösch, Bastian; Martin, Johannes; Eyselein, Jonathan; Langer, Jens; Wiesinger, Michael; Harder, Sjoerd (Organometallics, 2021)
The complex (DMAT)2Ba·(THF)2 (DMAT = 2-dimethylamino-α-trimethylsilylbenzyl) was prepared by a salt metathesis reaction between (DMAT)K and BaI2 in THF, and crystals were isolated in 83% yield. This monomeric complex dissolves well in aromatic or ethereal solvents and is also stable at higher temperatures in solution. Structural details and NMR parameters reveal a high degree of charge delocalization in the DMAT aryl ring. Comparison with identical Ca and Sr complexes, (DMAT)2Ae·(THF)2 (Ae = Ca and Sr), shows that the extent of delocalization increases down group 2: Ca < Sr < Ba. Due to chirality at the benzylic carbon, in solution the heterochiral R,S-isomer and homochiral R,R/S,S-isomers exist in equilibrium. A temperature-dependent NMR study gives an estimate of the Ae-C and Ae-N bond energies which decrease down the group: Ca > Sr > Ba. Although the DMAT carbanion is stabilized by resonance and negative hyperconjugation, (DMAT)2Ba·(THF)2 is still a very potent deprotonation reagent. Double deprotonation of Ph3SiNH2 gave the first Ba imido complex. A similar reaction using (DMAT)2Sr·(THF)2 gave the analogue Sr imido complex. Comparison with reported structures shows trends for the full series [(Ph3SiN)Ae·(THF)]4 (Ae = Mg, Ca, Sr, and Ba) which crystallize as tetramers with very stable, ionically bound heterocubane Ae4N4 cores.
CRIS-Team Scopus Importer:2021-06-04

A Rare Case of Magnesium Alkyl Mediated CO-to-Alkoxide Conversion - Townrow, Oliver; Richter, Tim; Langer, Jens; Harder, Sjoerd (Chemistry - A European Journal, 2024)
Alcohols can be produced by nucleophilic addition at the C=O functional group of ketones or aldehydes. Such C−C bond formations generally proceed smoothly and selective. In contrast, nucleophilic addition at carbon monoxide is considerably more complex and unselective due to the instability of polar metal acyl intermediates. Herein, we report a magnesium alkyl complex, stabilised with a dipyrromethenide ligand, and its reactivity with CO2 and CO. Whilst the reaction with CO2 gave the expected carboxylate, reaction with CO took a surprising course, resulting in an alkoxide by formation of three new C−C bonds in a single reaction. An intertwined experimental and computational approach sheds light on the unusual reactivity of a carbene intermediate.
CRIS-Team Scopus Importer:2024-11-29
Keywords: carbon monoxide; C−H activation; dipyrromethane; magnesium; metal alkyl

bis-Silyl-triazenide ligands in alkaline-earth metal chemistry - Knüpfer, Christian; Langer, Jens; Harder, Sjoerd (Zeitschrift für Anorganische und Allgemeine Chemie, 2023)
Monoanionic N,N-chelating triazenide ligands, [R-NNN-R]−, are compared to formamidinate or β-diketiminate ligands considerably less electron-donating and therefore potentially suitable for stabilizing electron rich metals in low oxidations states. A feature reported for silyl-substituted triazenide ligands, is their ability to eliminate N2 resulting in (R3Si)2N− anions. Here we describe a series of group 1 and 2 metal complexes with the very bulky bis-silyl-triazenide ligand [tBu3Si-NNN-SitBu3]−. Heteroleptic complexes could be isolated for Mg: [(tBu3Si)2N3]MgnBu2 or [(tBu3Si)2N3]MgI2, including its ether adducts. Despite bulky silyl substituents, the ligand did not stabilize heteroleptic [(tBu3Si)2N3]AeN(SiMe3)2 complexes for Ca, Sr and Ba and only homoleptic Ae[(tBu3Si)2N3]2 complexes were isolated. Thermal decomposition of these complexes did result in N2 elimination and formation of the expected amide complexes. Reduction of [(tBu3Si)2N3]MgI ⋅ (Et2O) with KC8 in Et2O led to the formation of a MgI complex with a Mg−Mg bond length of 2.902(1) Å. As only one of the Mg centres shows coordination with a Et2O ligand, this is a rare example of an asymmetric Mg−Mg bond. This MgI complex is rather unstable in benzene solution, likely due to reduction of the ligand system. Triazenide ligands are therefore not suitable for stabilization of group 2 metals in low oxidation states.
CRIS-Team Scopus Importer:2023-12-29
Keywords: Alkaline-earth; Low-valent; Reduction; Silyl; Triazene

Boosting Low-Valent Aluminum(I) Reactivity with a Potassium Reagent - Grams, Samuel; Eyselein, Jonathan; Langer, Jens; Färber, Christian; Harder, Sjoerd (Angewandte Chemie International Edition, 2020)
The reagent RK [R=CH(SiMe3)2 or N(SiMe3)2] was expected to react with the low-valent (DIPPBDI)Al (DIPPBDI=HC[C(Me)N(DIPP)]2, DIPP=2,6-iPr-phenyl) to give [(DIPPBDI)AlR]−K+. However, deprotonation of the Me group in the ligand backbone was observed and [H2C=C(N-DIPP)−C(H)=C(Me)−N−DIPP]Al−K+ (1) crystallized as a bright-yellow product (73 %). Like most anionic AlI complexes, 1 forms a dimer in which formally negatively charged Al centers are bridged by K+ ions, showing strong K+⋅⋅⋅DIPP interactions. The rather short Al–K bonds [3.499(1)–3.588(1) Å] indicate tight bonding of the dimer. According to DOSY NMR analysis, 1 is dimeric in C6H6 and monomeric in THF, but slowly reacts with both solvents. In reaction with C6H6, two C−H bond activations are observed and a product with a para-phenylene moiety was exclusively isolated. DFT calculations confirm that the Al center in 1 is more reactive than that in (DIPPBDI)Al. Calculations show that both AlI and K+ work in concert and determines the reactivity of 1.
CRIS-Team Scopus Importer:2020-07-10
Keywords: aluminum; C−H activation; density-functional calculations; low-valent complexes; potassium

Calcium-Catalyzed Arene C-H Bond Activation by Low-Valent Al-I - Brand, Steffen; Elsen, Holger; Langer, Jens; Grams, Samuel; Harder, Sjoerd (Angewandte Chemie International Edition, 2019)
The low-valent ss-diketiminate complex ((BDI)-B-DIPP)Al is stable in benzene but addition of catalytic quantities of [((BDI)-B-DIPP)CaH](2) at 20 degrees C led to ((BDI)-B-DIPP)Al(Ph)H ((BDI)-B-DIPP=CH[C(CH3)N-DIPP](2), DIPP=2,6-diisopropylphenyl). Similar Ca-catalyzed C-H bond activation is demonstrated for toluene or p-xylene. For toluene a remarkable selectivity for meta-functionalization has been observed. Reaction of ((BDI)-B-DIPP)Al(m-tolyl)H with I-2 gave m-tolyl iodide, H-2 and ((BDI)-B-DIPP)AlI2 which was recycled to ((BDI)-B-DIPP)Al. Attempts to catalyze this reaction with Mg or Zn hydride catalysts failed. Instead, the highly stable complexes ((BDI)-B-DIPP)Al(H)M((BDI)-B-DIPP) (M=Mg, Zn) were formed. DFT calculations on the Ca hydride catalyzed arene alumination suggest that a similar but more loosely bound complex is formed: ((BDI)-B-DIPP)Al(H)Ca((BDI)-B-DIPP). This is in equilibrium with the hydride bridged complex ((BDI)-B-DIPP)Al(mu-H)Ca((BDI)-B-DIPP) which shows strongly increased electron density at Al. The combination of Ca-arene bonding and a highly nucleophilic Al center are key to facile C-H bond activation.
CRIS-Team WoS Importer:2019-10-01

Calcium catalyzed enantioselective intramolecular alkene hydroamination with chiralC2-symmetric bis-amide ligands - Stegner, Philipp; Eyselein, Jonathan; Ballmann, Gerd; Langer, Jens; Schmidt, Jochen; Harder, Sjoerd (Dalton Transactions, 2021)
The chiral building block (R)-(+)-2,2′-diamino-1,1′-binaphthyl, (R)-BINAM, which is often used as backbone in privileged enantioselective catalysts, was converted to a series ofN-substituted proligandsR1-H2(R = CH2tBu, C(H)Ph2, PPh2, dibenzosuberane, 8-quinoline). After double deprotonation with strong Mg or Ca bases, a series of alkaline earth (Ae) metal catalystsR1-Ae·(THF)nwas obtained. Crystal structures of theseC2-symmetric catalysts have been analyzed by quadrant models which show that the ligands with C(H)Ph2, dibenzosuberane and 8-quinoline substituents should give the best steric discrimination for the enantioselective intramolecular alkene hydroamination (IAH) of the aminoalkenes H2C=CHCH2CR′2CH2NH2(CR′2= CPh2, CCy or CMe2). The dianionicR12−ligand inR1-Ae·(THF)nfunctions as reagent that deprotonates the aminoalkene substrate, while the monoanionic (R1-H)−ligand formed in this reaction functions as a chiral spectator ligand that controls the enantioselectivity of the ring closure reaction. Depending on the substituent R in the BINAM ligand, full cyclization of aminoalkenes to chiral pyrrolidine products as fast as 5 minutes was observed. Product analysis furnished enantioselectivities up to 57% ee, which marks the highest enantioselectivity reported for Ca catalyzed IAH. Higher selectivities are impeded by double protonation of theR12−ligand leading to complete loss of chiral information in the catalytically active species.
CRIS-Team Scopus Importer:2021-03-19

Carbon-Halogen Bond Activation with Powerful Heavy Alkaline Earth Metal Hydrides - Wiesinger, Michael; Rösch, Bastian; Knüpfer, Christian; Mai, Jonathan; Langer, Jens; Harder, Sjoerd (European Journal of Inorganic Chemistry, 2021)
Reaction of [(DIPePBDI)SrH]2 with C6H5X (X=Cl, Br, I) led to hydride-halogenide exchange (DIPePBDI=HC[(Me)CN-2,6-(3-pentyl)phenyl]2). Conversion rates increase with increasing halogen size (F<Cl<Br<I). Reaction of [(DIPePBDI)SrH]2 with C6H5F was slow and ill-defined but addition of C6H4F2 gave smooth hydride-fluoride exchange. After addition of THF the full range of Sr halogenides was structurally characterized: [(DIPePBDI)SrX ⋅ THF]2 (X=F, Cl, Br, I). Mixtures of AeN“2 and PhSiH3 in situ formed less defined but more robust Ae metal hydride clusters (AexN”yHz, Ae=Ca, Sr, Ba and N“=N(SiMe3)2) which are able to hydrodefluorinate C6H5F. Conversion rates increase with increasing metal size (Ca<Sr<Ba). Also alkylfluorides (1-F-hexane, F-cyclohexane, 1-F-adamantane) could be converted but, due to solubility problems of the Ba species, the fastest conversion was found for Sr. These AeN”2/PhSiH3 mixtures also converted SF6 at room temperature to give undefined decomposition products. Addition of Me6Tren to a SrN“2/PhSiH3 led to crystallization of [Sr6N”2H9 ⋅ (Me6Tren)3+][SrN“3−]; Me6Tren=tris[2-(dimethylamino)ethyl]amine). After hydrodefluorination, Sr6N”4F8 ⋅ (Me6Tren)2 was formed and structurally characterized. Dissolution in THF led to cluster growth and the larger cluster Sr16N“8F24 ⋅ (THF)12 is structurally characterized. DFT calculations support that hydrodehalogenation of halobenzenes follows a concerted nucleophilic aromatic substitution mechanism (cSNAr).
CRIS-Team Scopus Importer:2021-08-27
Keywords: Alkaline-earth metal; DFT calculation; Hydride; Hydrodehalogenation

Cationic Aluminium Complexes as Catalysts for Imine Hydrogenation - Friedrich, Alexander; Eyselein, Jonathan; Elsen, Holger; Langer, Jens; Pahl, Jürgen; Wiesinger, Michael; Harder, Sjoerd (Chemistry - A European Journal, 2021)
Strongly Lewis acidic cationic aluminium complexes, stabilized by β–diketiminate (BDI) ligands and free of Lewis bases, have been prepared as their B(C6F5)4− salts and were investigated for catalytic activity in imine hydrogenation. The backbone (R1) and N (R2) substituents on the R1,R2BDI ligand (R1,R2BDI=HC[C(R1)N(R2)]2) influence sterics and Lewis acidity. Ligand bulk increases along the row Me,DIPPBDI<Me,DIPePBDI≈tBu,DIPPBDI<tBu,DIPePBDI; DIPP=2,6-C(H)Me2-phenyl, DIPeP=2,6-C(H)Et2-phenyl. The Gutmann-Beckett test showed acceptor numbers of: (tBu,DIPPBDI)AlMe+ 85.6, (tBu,DIPePBDI)AlMe+ 85.9, (Me,DIPPBDI)AlMe+ 89.7, (Me,DIPePBDI)AlMe+ 90.8, (Me,DIPPBDI)AlH+ 95.3. Steric and electronic factors need to be balanced for catalytic activity in imine hydrogenation. Open, highly Lewis acidic, cations strongly coordinate imine rendering it inactive as a Frustrated Lewis Pair (FLP). The bulkiest cations do not coordinate imine but its combination is also not an active catalyst. The cation (tBu,DIPPBDI)AlMe+ shows the best catalytic activity for various imines and is also an active catalyst for the Tishchenko reaction of benzaldehyde to benzylbenzoate. DFT calculations on the mechanism of imine hydrogenation catalysed by cationic Al complexes reveal two interconnected catalytic cycles operating in concert. Hydrogen is activated either by FLP reactivity of an Al⋅⋅⋅imine couple or, after formation of significant quantities of amine, by reaction with an Al⋅⋅⋅amine couple. The latter autocatalytic Al⋅⋅⋅amine cycle is energetically favoured.
CRIS-Team Scopus Importer:2021-05-07
Keywords: Aluminium; cations; DFT; hydrogenation; imine

Cationic Heterobimetallic Mg(Zn)/Al(Ga) Combinations for Cooperative C-F Bond Cleavage - Friedrich, Alexander; Eyselein, Jonathan; Langer, Jens; Färber, Christian; Harder, Sjoerd (Angewandte Chemie International Edition, 2021)
Low-valent ((BDI)-B-Me)Al and ((BDI)-B-Me)Ga and highly Lewis acidic cations in [((BDI)-B-tBu)M+.C6H6][(B(C6F5)(4)(-)] (M=Mg or Zn, (BDI)-B-Me=HC[C(Me)N-DIPP](2), (BDI)-B-tBu=HC[C(tBu)N-DIPP](2), DIPP=2,6-diisopropylphenyl) react to heterobimetallic cations [((BDI)-B-tBu)Mg-Al((BDI)-B-Me)(+)], [((BDI)-B-tBu)Mg-Ga((BDI)-B-Me)(+)] and [((BDI)-B-tBu)Zn-Ga((BDI)-B-Me)(+)]. These cations feature long Mg-Al (or Ga) bonds while the Zn-Ga bond is short. The [((BDI)-B-tBu)Zn-Al((BDI)-B-Me)(+)] cation was not formed. Combined AIM and charge calculations suggest that the metal-metal bonds to Zn are considerably more covalent, whereas those to Mg should be described as weak Al-I(or Ga-I)-> Mg2+ donor bonds. Failure to isolate the Zn-Al combination originates from cleavage of the C-F bond in the solvent fluorobenzene to give ((BDI)-B-tBu)ZnPh and ((BDI)-B-Me)AlF+ which is extremely Lewis acidic and was not observed, but ((BDI)-B-Me)Al(F)-(mu-F)-(F)Al((BDI)-B-Me)(+) was verified by X-ray diffraction. DFT calculations show that the remarkably facile C-F bond cleavage follows a dearomatization/rearomatization route.
CRIS-Team WoS Importer:2021-06-25

Chromium(II) Alkylcyclopentadienyl Complexes with Carbon or Hydride Donor Ligands - Smytschkow, Igor; Gidt, Wjatscheslaw; Sun, Yu; Langer, Jens; Boettcher, Tobias; Kubickova, Lenka; Kaman, Ondrej; Sitzmann, Helmut (Organometallics, 2021)
Alkylcyclopentadienylchromium(II) bromide dimers [Cp‴Cr(μ-Br)]2 and [5CpCr(μ-Br)]2 (Cp‴ = tri(tert-butyl)cyclopentadienide, 5Cp = pentaisopropylcyclopentadienide) have been used as starting compounds for replacement of bromide with methyl, hydride, phenyl, phenylacetylide, cyanide, or tetrahydroaluminate anions and afforded dinuclear chromium(II) complexes except for cyanide and tetrahydroaluminate, where tetranuclear products were isolated. Mononuclear chromium complexes have been synthesized by N-heterocyclic carbene addition to the bromide complex or by bromide substitution with a cyclopentadienyl or another alkylcyclopentadienyl ligand. Strong antiferromagnetic coupling with J1,2 = -206 cm-1 of two high-spin Cr(II) central atoms has been found for the dinuclear hydride [Cp‴Cr(μ-H)]2, which was obtained during reactions with isopropylmagnesium chloride via β-hydride elimination and was also found after attempted potassium reduction of the chromium(II) starting compound. Diamagnetic behavior was observed only for the tetranuclear aluminumtetrahydro-tri(tert-butyl)chromate(II).
CRIS-Team Scopus Importer:2021-09-24

Chromium(III) and Chromium(II) Phenolate Complexes with Bulky Alkylcyclopentadienyl Ligands - Smytschkow, Igor; Gidt, Wjatscheslaw; Kunz, Christoph; Sun, Yu; Langer, Jens; Oelkers, Benjamin; Böttcher, Tobias; Sitzmann, Helmut (European Journal of Inorganic Chemistry, 2019)
The chromium(II) tricarbonyl methyl complex [Cp′′′Cr(CO)3CH3] (1, Cp′′′ = η5-C5H2tBu3-1,2,4) was obtained from chromium hexacarbonyl, NaCp′′′, and methyl iodide. 1 was found to establish an equilibrium with the dicarbonyl acetyl isomer [Cp′′′Cr(CO)2(COCH3)] in solution via reversible, slightly endothermic methyl migration from chromium to a carbonyl ligand with ΔH ca. 3.6 kJ/mol and Ea ca. 49.5 kJ/mol. Phosphorus pentachloride oxidized 1 to the green, dinuclear tetrachloro complex [Cp′′′CrCl(µ-Cl)]2 (2), which was crystallized as the blue-green chromium(III) half sandwich complex [Cp′′′CrCl2(THF)] (3) in the presence of tetrahydrofuran vapor. Attempted sublimation of the known chromium(II) iodo complex [4CpCr(µ-I)]2 resulted in a redox reaction with formation of the chromium(III) iodo dimer [4CpCrI(µ-I)]2, whose tri(tert-butyl)cyclopentadienyl derivative [Cp′′′CrI(µ-I)]2 (4) could also be prepared by oxidation of [Cp′′′Cr(µ-I)]2 with iodine. The chromium(III) bis(2,6-diisopropylphenolate) complex [4CpCr(OC6H3iPr2-2,6)2] (5) was obtained from chromium trichloride in a one pot reaction with sodium tetraisopropylcyclopentadienide, followed by sodium 2,6-diisopropylphenolate. The chromium(III) starting compound 2 reacted with 2,6-diisopropylphenolate to the Cp′′′ derivative [Cp′′′Cr(OC6H3iPr2-2,6)2] (6). The chromium(II) starting compound [Cp′′′Cr(µ-Br)]2 afforded the phenolate-bridged chromium(II) dimer [Cp′′′Cr(µ-OC6H5)]2 (7) upon treatment with sodium phenolate, while the product of the analogous reaction with 2,6-di(tert-butyl)phenolate was the mononuclear tetrahydrofuran adduct [Cp′′′Cr(OC6H3tBu2-2,6)(THF)] (8).
CRIS-Team Scopus Importer:2019-06-25
Keywords: Chromium; Cyclopentadienyl ligands; Ligand effects; Magnetic properties; Structure elucidation

Comparison of Magnesium and Zinc in Cationic π-Arene and Halobenzene Complexes - Friedrich, Alexander; Eyselein, Jonathan; Langer, Jens; Harder, Sjoerd (Organometallics, 2021)
The reaction of (tBuBDI)ZnEt with [Ph3C+][B(C6F5)4-] yielded the cation (tBuBDI)Zn+ (tBuBDI = CH[C(tBu)N-DIPP]2, DIPP = 2,6-diisopropylphenyl). The cation is sterically too shielded to interact with the ion B(C6F5)4- but forms complexes with arenes (benzene, toluene, m-xylene) or halobenzenes (PhX: X = F, Cl, Br, I). Crystal structures of these complexes are compared with those of the corresponding Mg complexes. Although Mg2+ and Zn2+ are of equal size, the Zn···arene and Zn···XPh contacts are generally 0.1-0.2 Å shorter than comparable contacts to (tBuBDI)Mg+. This originates from differences in bond character: bonding to Mg has a more electrostatic nature. A major difference between Mg and Zn is observed for PhF complexation. While the hard Mg2+ cation prefers Mg···FPh bonding, the softer Zn2+ shows a Zn···( π)PhF interaction. Heavier halobenzenes with softer halogens (Cl, Br, I) show Zn···XPh bonding. DFT calculations on (tBuBDI)Zn+···XPh (X = F, Cl, Br, I) show decreasing Zn···X-Ph angles from PhF to PhI on account of the increase in the halogen's σ-hole. Zn···XPh interactions result in C-X bond lengthening, but C-X bond activation is less pronounced than in corresponding Mg···XPh complexes. Weak (tBuBDI)Zn+···XPh bonding could not be detected in solution but is believed to play a role in the functionalization of organohalides by Zn reagents.
CRIS-Team Scopus Importer:2021-03-26

d–d Dative Bonding Between Iron and the Alkaline-Earth Metals Calcium, Strontium, and Barium - Stegner, Philipp; Färber, Christian; Oetzel, Jan; Siemeling, Ulrich; Wiesinger, Michael; Langer, Jens; Pan, Sudip; Holzmann, Nicole; Frenking, Gernot; Albold, Uta; Sarkar, Biprajit; Harder, Sjoerd (Angewandte Chemie International Edition, 2020)
Double deprotonation of the diamine 1,1′-(tBuCH2NH)-ferrocene (1-H2) by alkaline-earth (Ae) or EuII metal reagents gave the complexes 1-Ae (Ae=Mg, Ca, Sr, Ba) and 1-Eu. 1-Mg crystallized as a monomer while the heavier complexes crystallized as dimers. The Fe⋅⋅⋅Mg distance in 1-Mg is too long for a bonding interaction, but short Fe⋅⋅⋅Ae distances in 1-Ca, 1-Sr, and 1-Ba clearly support intramolecular Fe⋅⋅⋅Ae bonding. Further evidence for interactions is provided by a tilting of the Cp rings and the related 1H NMR chemical-shift difference between the Cp α and β protons. While electrochemical studies are complicated by complex decomposition, UV/Vis spectral features of the complexes support Fe→Ae dative bonding. A comprehensive bonding analysis of all 1-Ae complexes shows that the heavier species 1-Ca, 1-Sr, and 1-Ba possess genuine Fe→Ae bonds which involve vacant d-orbitals of the alkaline-earth atoms and partially filled d-orbitals on Fe. In 1-Mg, a weak Fe→Mg donation into vacant p-orbitals of the Mg atom is observed.
CRIS-Team Scopus Importer:2020-07-10
Keywords: alkaline-earth metals; ferrocene; metal–metal bonding; theoretical chemistry

Developing bulky P-alkene ligands: stabilization of copper complexes with 14 valence electrons - Grasruck, Alexander; Parla, Giorgio; Heinemann, Frank Wilhelm; Langer, Jens; Herrera, Alberto Cesar; Friess, Stefan; Schmid, Guenter; Dorta, Romano (New Journal of Chemistry, 2022)
The new mono dibenzo[b,f]-azepinyl substituted P-alkene ligands 7-9, 20, and 21 were used to synthesize monomeric and dimeric Cu(i) complexes by using metal to ligand ratios of 2 : 1 and 1 : 1, respectively. With the super-bulky tris dibenzo[b,f]-azepinyl substituted P-alkenes 21, only monomers form with a 1 : 1 stoichiometry. Cationic complexes were obtained either by employing [Cu(OTf)](2)& BULL;C6H6 as the starting material, or by chloride abstractions from the monomeric chlorido complexes with NaB(Ar-F)(4) or TlBF4, whereas with silver salts only Ag(i)-P-alkene complexes were isolated by transmetallation. Chloride abstraction with NaB(Ar-F)(4) gave the 14 ve cationic complex 18, which shows no alkene coordination and a bent coordination geometry due to the steric pressure exerted by the ligand. The buried volumes of the ligands (calculated from X-ray diffraction data) increase in the order 8 < 7 < 9 < 20 < 21 with the last displaying a staggering V-bur of 60.6% (the crystallographic Tolman angle in copper complex 23 amounts to 229 & DEG;). The bulkiest ligand (21) allowed us to isolate and structurally characterize rare examples of 14 ve Cu(i) complexes, namely the neutral chloride 23 and, after salt metathesis with NaB(Ar-F)(4), the chlorido bridged dinuclear cation 26 exhibiting short Cu-Cl bonds.
CRIS-Team WoS Importer:2023-01-27

Dibenzoazepine hydrazine is a building block for N-alkene hybrid ligands: exploratory syntheses of complexes of Cu, Fe, and Li - Grasruck, Alexander; Schall, Kristina; Heinemann, Frank Wilhelm; Langer, Jens; Herrera, Alberto; Frieß, Sibylle; Schmid, Günter; Dorta, Romano (Dalton Transactions, 2024)
The new hydrazine 5H-dibenzo[b,f]azepin-5-amine (2) reacts with P- and Si-electrophiles via deprotonation to afford P(iii)-, P(v)-, and TMS-hydrazides 3-8 and with carbonyl electrophiles via acid-free condensation to the N-substituted hydrazones 9-12 that are potential N-alkene ligands. While β-ketohydrazone 9 and α-dihydrazone 10 react with [Mes(Cu)]4, [Cu(NCCCH3)4]2PF6, and FeCl2(THF)1.5 to afford complexes devoid of alkene interaction, [Cu(OTf)]2·C6H6 reacts with the α-keto hydrazone 11 or with N,N dimethyl-hydrazone 12 to form the neutral dimeric Cu(i) complex 18 with bridging Cu(i)-alkene interactions or the tetrahedral cationic complex 19 in which 12 binds as a bidentate hydrazone-alkene ligand, respectively. The surprising stability of the alkene coordination in complexes 18 and 19 prevents substitutions with, e.g., PPh3
CRIS-Team Scopus Importer:2024-05-17

Dibenzotropylidene Substituted Ligands for Early Main Group Metal-Alkene Bonding - Martin, Johannes; Langer, Jens; Wiesinger, Michael; Elsen, Holger; Harder, Sjoerd (European Journal of Inorganic Chemistry, 2020)
New N-ligands with TROP-substituents are introduced (TROP = [5H]dibenzo[a,d]cyclohepten-5-yl): (TROP)(DIPP)N (DIPP = 2,6-diisopropylphenyl), TROPBDI (HC[C(Me)N-TROP]2) and the β-diketiminate ligand TROP–DIPPBDI with TROP and DIPP substituents at N. Several Li, Mg, Ca and Zn complexes with these ligands have been isolated and were characterized by X-ray diffraction. While TROP-substituents in the protonated ligands show endo-exo exchange, TROP-substituents in the metal complexes are in endo-conformation due to metal···alkene bonding. Short contacts between the metal and the TROP alkene unit are observed and some of these are the shortest reported; (TROPBDI)Li: Li···C 2.416(3) Å, [(TROP)(DIPP)N]2Ca: Ca···C 2.742(2) Å. TROPBDI shows superior metal shielding properties to the Li complex with a buried volume of VB = 78.7 %. DFT calculations on [(TROP)(DIPP)N]2Mg show a minimum with asymmetric Mg···alkene bonding. Symmetric Mg···alkene bonding is a transition state 1.9 kcal/mol higher in energy. Asymmetry in alkene-Mg bonding is explained by an ion-induced polarization of the C=C bond and electrostatic Mg2+···(δ-)C=C(δ+) attraction. The TROP-substituent stabilizes low valent radical species but attempts to isolate (TROPBDI)Mg· or (TROPBDI)Zn· by reduction of the iodide precursors failed. Intensely black coloured raw products hint towards formation of radical species. Several radical decomposition products have been structurally characterized.
CRIS-Team Scopus Importer:2020-07-17
Keywords: Amides; Early main group metals; Metal-alkene bonding; Radicals; β-Diketiminate

Dinitrogen complexation and reduction at low-valent calcium - Rösch, Bastian; Gentner, Thomas; Langer, Jens; Färber, Christian; Eyselein, Jonathan; Zhao, L.; Ding, C.; Frenking, G.; Harder, Sjoerd (Science, 2021)
Here we report that attempted preparation of low-valent CaI complexes in the form of LCa-CaL (where L is a bulky b-diketiminate ligand) under dinitrogen (N2) atmosphere led to isolation of LCa(N2)CaL, which was characterized crystallographically. The N22- anion in this complex reacted in most cases as a very potent two-electron donor. Therefore, LCa(N2)CaL acts as a synthon for the low-valent CaI complex LCa-CaL, which was the target of our studies. The N22- anion could also be protonated to diazene (N2H2) that disproportionated to hydrazine and N2. The role of Ca d orbitals for N2 activation is discussed.
CRIS-Team Scopus Importer:2021-03-26

Dinuclear Zn Complex: Phenoxyl Radical Formation Driven by Superoxide Coordination - Squarcina, Andrea; Fehn, Dominik; Senft, Laura; Langer, Jens; Ivanović-Burmazović, Ivana (Zeitschrift für Anorganische und Allgemeine Chemie, 2021)
The dinuclear zinc complex Zn2L2 (HL=2-[[di(2-pyridyl)methyl](methyl)amino]methylphenol) has been synthesized and isolated as colorless crystals. The interaction of the compound with superoxide in anhydrous organic solvents has been evaluated by CV, stopped-flow Uv-vis, EPR and ESI-MS suggesting the binding and the activation of the coordinated superoxide, thanks to the Lewis acidity of the Zn(II) centers. The results obtained in this study highlight the formation of a Zn2L2−O2.− intermediate and a metastable phenoxyl-radical driven by the coordinated superoxide.
CRIS-Team Scopus Importer:2021-05-14
Keywords: electron transfer; Lewis acid; phenoxyl radical; superoxide; zinc complex

Dipyrromethene as a Ligand for the Stabilization of Low-Valent Gallium Complexes - Richter, Tim; Thum, Stefan; Vilpas, Timothy; Townrow, Oliver; Klerner, Lukas; Langer, Jens; Harder, Sjoerd (Organometallics, 2024)
We investigated the low-valent chemistry of Al and Ga with the ligand tBuDPM, a dipyrromethene ligand scaffold with two large tBu groups in the flanking 1- and 9-positions and a mesityl group in the backbone 5-position. Attempted synthesis of (tBuDPM)AlI by reduction of (tBuDPM)AlI2 with KC8 failed. However, reduction of (tBuDPM)GaI2 (1) with K/KI led to successful isolation of (tBuDPM)GaI (3). The GaII intermediate in the reduction process crystallized as a digallane: [(tBuDPM)GaI]2 (2). Also, 3 crystallized as a dinuclear complex with a Ga-Ga bond. However, in a benzene solution, the 3 dissociates into two mononuclear complexes. Reaction of a benzene solution of (tBuDPM)GaI with excess Me3SiN3 gave the tetrazagallole product (tBuDPM)Ga[N4(SiMe3)2] (4) and not the alternative azide-amide product (tBuDPM)Ga(N3)[N(SiMe3)2], which according to calculations is thermodynamically considerably more stable. Theoretical investigations on the nature of the Ga-Ga bonds in 2 and 3 and the mechanism for selective formation of 4 have been included.
CRIS-Team Scopus Importer:2024-06-28

Diverse Reactivity of a Ca(I) Synthon - Mai, Jonathan; Rösch, Bastian; Langer, Jens; Grams, Samuel; Morasch, Michael; Harder, Sjoerd (European Journal of Inorganic Chemistry, 2023)
Low-valent MgI complexes like (BDI)Mg−Mg(BDI) have found wide-spread application as specialty reducing agents (BDI=β-diketiminate). Also their redox reactivity was extensively investigated. In contrast, attempts to isolate similar CaI complexes led to reduction of the aromatic solvents or N2. Complex (DIPePBDI)Ca(μ6,μ6-C6H6)Ca(DIPePBDI) (VIII) should be regarded a CaII complex with a bridging C6H62− dianion (DIPePBDI=HC[C(Me)N-DIPeP]2, DIPeP=2,6-C(H)Et2-phenyl). It can react as a CaI synthon by releasing benzene and two electrons. Herein we describe the reactivity of VIII with benzene, biphenyl, naphthalene, anthracene, COT, Ph3SiCl, PhSiH3, a (BDI)AlI2 complex, H2, PhX (X=F, Cl, Br, I), tBuOH and tBuCH2I. The C6H62− dianion in VIII can react as a 2e− source, a nucleophile or a Brønsted base. In some cases radical reactivity cannot be excluded. Crystal structures of (DIPePBDI)Ca(μ8,μ8-COT)Ca(DIPePBDI) (1) and [(DIPePBDI)CaX ⋅ (THF)]2 (X=F, Cl, Br, I) (2–5) are described.
CRIS-Team Scopus Importer:2023-09-15
Keywords: Calcium; low-valent compounds; reactivity; reduction; β-diketiminate

Evolution of a ‘privileged’ P-alkene ligand: added planar chirality beats BINOL axial chirality in catalytic asymmetric C-C bond formation - Leinauer, Luisa; Parla, Giorgio; Messelberger, Julian; Herrera, Alberto Cesar; Heinemann, Frank Wilhelm; Langer, Jens; Chuchelkin, Ilya; Grasruck, Alexander; Frieß, Sibylle; Chelouan, Ahmed; Gavrilov, Konstantin; Dorta, Romano (Chemical Communications, 2023)
Alkene planar chirality is introduced in the ‘privileged’ P-alkene phosphoramidite ligand 1. The resulting diastereomeric ligands (pR,R)-5 and (pS,R)-5 form optically pure complexes of Rh(i) and Pd(ii), which catalyze conjugate additions of boron C-nucleophiles to enones and allylic alkylations, respectively. In the Rh-catalyzed reaction, the planar chirality of the alkene exerts absolute enantiocontrol over the potent BINOL auxiliary.
CRIS-Team Scopus Importer:2023-12-15

Formation and Reactivity of Non-Stabilized Monomeric Alumoxane Intermediates - Grams, Samuel; Maurer, Johannes; Patel, Neha; Langer, Jens; Harder, Sjoerd (Zeitschrift für Anorganische und Allgemeine Chemie, 2022)
Several methods for the oxidation of the β-diketiminate AlI complexes (BDI)Al and (BDI*)Al with O2, Et3P=O or N2O are presented (BDI=HC[C(Me)N(DIPP)]2, DIPP=2,6-diisopropylphenyl; BDI*=HC[C(tBu)N(DIPP)]2). The selectivity of alumoxane formation depends strongly on the nature of the β-diketiminate ligand, the experimental procedure and the solvent. The mononuclear alumoxanes (BDI)Al=O and (BDI*)Al=O are highly reactive intermediates that cannot be isolated but either aggregate to give less reactive dimers or decompose by internal C−H activation of a backbone Me group or an iPr group. Ethereal solvents like Et2O react with alumoxanes to give (BDI)Al(OEt)OH and ethylene by β-H elimination. In case of N2O oxidation, subsequent reaction with a second equivalent of N2O to form the hyponitrite complexes (BDI)Al(N2O2) and (BDI*)Al(N2O2) is observed. Details of the alumoxane formation, reactivity and decomposition have been obtained by DFT calculations. These calculations also underscore their rather bipolar character, represented by the resonance structure (BDI)Al+−O−, and estimate the σ- and π-bond character of the Al=O bond at circa 76 % and 24 %, respectively.
CRIS-Team Scopus Importer:2022-03-11
Keywords: Aluminium; Alumoxane; DFT calculations; Low-valent; β-diketiminate

Heterobimetallic alkaline earth metal–metal bonding - Mai, Jonathan; Maurer, Johannes; Langer, Jens; Harder, Sjoerd (Nature Synthesis, 2023)
Low-oxidation-state complexes of type (BDI)Mg–Mg(BDI) (BDI, β-diketiminate) show broad reactivity, finding application as soluble, universal reducing agents, enriching the field of early main group metal chemistry. Attempts to isolate similar, but considerably more reactive, Ca–Ca bound complexes have so far failed. As the metal–metal bond strength descending group 2 rapidly decreases, BDI complexes of the heavier AeI (alkaline earth) ions (Ae = Ca, Sr, Ba) probably exist as (BDI)Ae· radicals of untamed reactivity. Here we describe a facile method to prepare stable but highly reactive complexes with heterobimetallic Mg–Ae bonds. Mixing [(BDI)MgˉNa+]2 and [Ae(NR2)2]2 dimers led to anion–cation exchange and exclusive formation of mixed species: (BDI)MgˉNa+/Ae(NR2)2 (Ae = Ca, Sr, Ba; R = SiMe3). Crystal structures feature examples of Mg–Ca and Mg–Sr bonding with formal oxidation states of Mg0–AeII. Best described as polarized Mgδˉ–Aeδ+ bonds, these complexes show potential as alkane-soluble reductants for bond activation, which readily react with benzene by C–H bond cleavage and are oxidized to discrete complexes with N2O. [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2023-12-15

Heteroleptic Heavier Alkaline Earth Metal Amide Complexes Stabilized by a Superbulky β-Diketiminate Ligand - Gentner, Thomas; Rösch, Bastian; Thum, Katharina; Langer, Jens; Ballmann, Gerd; Pahl, Jürgen; Donaubauer, Wolfgang; Hampel, Frank; Harder, Sjoerd (Organometallics, 2019)
Heteroleptic alkaline earth metal (Ae = Ca, Sr, Ba) amide complexes with the superbulky β-diketiminate ligand DIPePBDI (CH[C(Me)N-DIPeP]2, DIPeP = 2,6-di-iso-pentylphenyl) have been prepared by direct deprotonation of DIPePBDI-H with either AeN′′2 or AeN′′2·(THF)2 (N′′ = N(SiMe3)2). Despite long reaction times of 5-14 days, this convenient one-step synthetic method has the major advantage that metal-pure products are obtained in generally quantitative yields. All (DIPePBDI)AeN′′ and (DIPePBDI)AeN′′·THF complexes are monomeric and stabilized by agostic metal···Me3Si and metal···iso-pentyl interactions. They are highly soluble in toluene and indefinitely stable toward ligand scrambling, even after 2 weeks at 140 °C. The same series with the smaller DIPPBDI ligand (CH[C(Me)N-DIPP]2, DIPP = 2,6-di-iso-propylphenyl) could, except for Ca, also be prepared by direct ligand deprotonation. The (DIPPBDI)CaN′′ and (DIPPBDI)CaN′′·THF complexes are stable toward ligand exchange up to 110 °C. Whereas THF-free (DIPPBDI)SrN′′ and (DIPPBDI)BaN′′ decompose at 50 and 20 °C, respectively, their THF adducts were found to be stable up to 60 °C. This is, however, strongly dependent on complex purity. Slight hydrolysis or contamination with KN′′ accelerates ligand scrambling. Therefore, partial hydrolysis and salt metathesis routes that involve KN′′ should be avoided when synthesizing heteroleptic complexes of the heavier Ae metals.
CRIS-Team Scopus Importer:2019-07-09

Heterometallic Mg−Ba Hydride Clusters in Hydrogenation Catalysis - Wiesinger, Michael; Knüpfer, Christian; Elsen, Holger; Mai, Jonathan; Langer, Jens; Harder, Sjoerd (ChemCatChem, 2021)
Reaction of a MgN“2/BaN”2 mixture (N“=N(SiMe3)2) with PhSiH3 gave three unique heterometallic Mg/Ba hydride clusters: Mg5Ba4H11N”7 ⋅ (benzene)2 (1), Mg4Ba7H13N“9 ⋅ (toluene)2 (2) and Mg7Ba12H26N”12 (3). Product formation is controlled by the Mg/Ba ratio and temperature. Crystal structures are described. While 3 is fully insoluble, clusters 1 and 2 retain their structures in aromatic solvents. DFT calculations and AIM analyses indicate highly ionic bonding with Mg−H and Ba−H bond paths. Also unusual H−⋅⋅⋅H− bond paths are observed. Catalytic hydrogenation with MgN“2, BaN”2 and the mixture MgN“2/BaN”2 has been studied. Whereas MgN“2 is only active in imine hydrogenation, alkene and alkyne hydrogenation needs the presence of Ba. The catalytic activity of the MgN”2/BaN“2 mixture lies in general between that of its individual components and strong cooperative effects are not evident.
CRIS-Team Scopus Importer:2021-09-17
Keywords: alkaline earth metal; catalysis; DFT calculations; heterometallic; hydride

Highly Active Superbulky Alkaline Earth Metal Amide Catalysts for Hydrogenation of Challenging Alkenes and Aromatic Rings - Martin, Johannes; Knüpfer, Christian; Eyselein, Jonathan; Färber, Christian; Grams, Samuel; Langer, Jens; Thum, Katharina; Wiesinger, Michael; Harder, Sjoerd (Angewandte Chemie International Edition, 2020)
Two series of bulky alkaline earth (Ae) metal amide complexes have been prepared: Ae[N(TRIP)2]2 (1-Ae) and Ae[N(TRIP)(DIPP)]2 (2-Ae) (Ae=Mg, Ca, Sr, Ba; TRIP=SiiPr3, DIPP=2,6-diisopropylphenyl). While monomeric 1-Ca was already known, the new complexes have been structurally characterized. Monomers 1-Ae are highly linear while the monomers 2-Ae are slightly bent. The bulkier amide complexes 1-Ae are by far the most active catalysts in alkene hydrogenation with activities increasing from Mg to Ba. Catalyst 1-Ba can reduce internal alkenes like cyclohexene or 3-hexene and highly challenging substrates like 1-Me-cyclohexene or tetraphenylethylene. It is also active in arene hydrogenation reducing anthracene and naphthalene (even when substituted with an alkyl) as well as biphenyl. Benzene could be reduced to cyclohexane but full conversion was not reached. The first step in catalytic hydrogenation is formation of an (amide)AeH species, which can form larger aggregates. Increasing the bulk of the amide ligand decreases aggregate size but it is unclear what the true catalyst(s) is (are). DFT calculations suggest that amide bulk also has a noticeable influence on the thermodynamics for formation of the (amide)AeH species. Complex 1-Ba is currently the most powerful Ae metal hydrogenation catalyst. Due to tremendously increased activities in comparison to those of previously reported catalysts, the substrate scope in hydrogenation catalysis could be extended to challenging multi-substituted unactivated alkenes and even to arenes among which benzene.
CRIS-Team Scopus Importer:2020-04-03
Keywords: Alkaline Earth Metals; Alkenes; Aromatic rings; DFT calculations; Hydrogenation

Insights into LiAlH4 Catalyzed Imine Hydrogenation - Elsen, Holger; Langer, Jens; Ballmann, Gerd; Wiesinger, Michael; Harder, Sjoerd (Chemistry - A European Journal, 2020)
Commercial LiAlH4 can be used in catalytic quantities in the hydrogenation of imines to amines with H2. Combined experimental and theoretical investigations give deeper insight in the mechanism and identifies the most likely catalytic cycle. Activity is lost when Li in LiAlH4 is exchanged for Na or K. Exchanging Al for B or Ga also led to dramatically reduced activities. This indicates a heterobimetallic mechanism in which cooperation between Li and Al is crucial. Potential intermediates on the catalytic pathway have been isolated from reactions of MAlH4 (M=Li, Na, K) and different imines. Depending on the imine, double, triple or quadruple imine insertion has been observed. Prolonged reaction of LiAlH4 with PhC(H)=NtBu led to a side-reaction and gave the double insertion product LiAlH2[N]2 ([N]=N(tBu)CH2Ph) which at higher temperature reacts further by ortho-metallation of the Ph ring. A DFT study led to a number of conclusions. The most likely catalyst for hydrogenation of PhC(H)=NtBu with LiAlH4 is LiAlH2[N]2. Insertion of a third imine via a heterobimetallic transition state has a barrier of +23.2 kcal mol−1 (ΔH). The rate-determining step is hydrogenolysis of LiAlH[N]3 with H2 with a barrier of +29.2 kcal mol−1. In agreement with experiment, replacing Li for Na (or K) and Al for B (or Ga) led to higher calculated barriers. Also, the AlH4− anion showed very high barriers. Calculations support the experimentally observed effects of the imine substituents at C and N: the lowest barriers are calculated for imines with aryl-substituents at C and alkyl-substituents at N.
CRIS-Team Scopus Importer:2020-12-04
Keywords: DFT; heterobimetallic; hydride; hydrogenation; imine

Intramolecular Alkene Hydroamination with Hybrid Catalysts Consisting of a Metal Salt and a Neutral Organic Base - Stegner, Philipp; Fischer, Christian; Nguyen, D. Thao; Rösch, Andreas; Penafiel, Johanne; Langer, Jens; Wiesinger, Michael; Harder, Sjoerd (European Journal of Inorganic Chemistry, 2020)
Hybrid catalysts consisting of alkaline earth iodides (AeI2) and the Schwesinger base tBuP4 catalyse the intramolecular alkene hydroamination of H2C=CHCH2CR2CH2NH2 [CR2=CPh2, C(CH2)5, CMe2]. Activities decrease along the row: Ca > Sr >> Mg > Ba. Hybrid catalysts consisting of tBuP4 and ZnI2, AlI3, FeCI3 or NaI were found to be fully inactive. Also, the hybrid catalyst tBuP3/CaI2 was not active which means that the base strength of the non-nucleophilic organic base must be higher than that of tBuP3 (pKa BH+ = 38.6). Combinations of tBuP4 with CaX2 (X = Cl, Br, OiPr, OTf, NTf2) were found to be fully inactive which may in part be explained by poor solubility. The hybrid catalysis method is therefore limited to the combination tBuP4/CaI2 but the iodide ligands may be partially or fully replaced by chiral ligands. Chiral modifications of the hybrid catalysts gave in intramolecular alkene hydroamination ee values up to 33 %.
CRIS-Team Scopus Importer:2020-09-11
Keywords: Calcium; Homogeneous catalysis; Intramolecular alkene hydroamination; Schwesinger bases

Ir(IV) Sulfoxide-Pincer Complexes by Three-Electron Oxidative Additions of Br-2 and I-2. Unprecedented Trap-Free Reductive Elimination of I-2 from a formal d(5) Metal - Frieß, Sibylle; Benyak, Anna; Herrera, Alberto Cesar; Escalona Bauza, Ana Melissa; Heinemann, Frank Wilhelm; Langer, Jens; Fehn, Dominik; Pividori, Daniel Maximilian; Grasruck, Alexander; Munz, Dominik; Meyer, Karsten; Dorta, Romano (Inorganic Chemistry, 2022)
Oxidative addition of 1.5 equiv of bromine or iodine to a Ir(I) sulfoxide pincer complex affords the corresponding Ir(IV) tris-bromido or tris-iodido complexes, respectively. The unprecedented trap-free reductive elimination of iodine from the Ir(IV)-iodido complex is induced by coordination of ligands or donor solvents. In the case of added I-, the isostructural tris-iodo Ir(III)-ate complex is quickly generated, which then can be readily reoxidized to the Ir(IV)-iodido complex with FcPF(6) or electrochemically. DFT calculations indicate an "inverted ligand field" in the Ir(IV) complexes and favor dinuclear pathways for the reductive elimination of iodine from the formal metal center.
CRIS-Team WoS Importer:2022-01-21

Large decanuclear calcium and strontium hydride clusters - Martin, Johannes; Eyselein, Jonathan; Langer, Jens; Elsen, Holger; Harder, Sjoerd (Chemical Communications, 2020)
Two large decanuclear hydride clusters of the general formula Ae10H16[N(R)R']4·(PMDTA)2 (Ae = Ca, Sr) were isolated. Both derivatives feature a [Ae10H16]4+ core, consisting of two edge shared metal octahedra with interstitial hydrides, while the other hydrides cap triangular faces.
CRIS-Team Scopus Importer:2020-08-21

Lewis acidic alkaline earth metal complexes with a perfluorinated diphenylamide ligand - Fischer, Christian; Rösch, Andreas; Elsen, Holger; Ballmann, Gerd; Wiesinger, Michael; Langer, Jens; Färber, Christian; Harder, Sjoerd (Dalton Transactions, 2019)
Alkaline earth metal (Ae) chemistry with the anion [N(C 6 F 5 ) 2 ] - has been explored. Deprotonation of the amine (C 6 F 5 ) 2 NH, abbreviated in here as N F H, with 0.5 equivalent of AeN′′ 2 (N′′ = N(SiMe 3 ) 2 ) is fast and gave, dependent on the solvent, the complexes AeN F 2 , AeN F 2 ·(THF) 2 and AeN F 2 ·(Et 2 O) 2 (Ae = Mg, Ca, Sr). Using a 1/1 ratio, mixed amide complexes were obtained: N F AeN′′ (Ae = Mg, Ca, Sr). Crystal structures of the monomers AeN F 2 ·(THF) 2 (Ae = Mg, Ca, Sr) and AeN F 2 ·(Et 2 O) 2 (Ae = Mg, Ca) are presented and compared with those of AeN′′ 2 ·(THF) 2 . In addition, crystal structures of the homoleptic dimer (MgN F 2 ) 2 and the heteroleptic dimers (N F AeN′′) 2 (Ae = Mg, Ca, Sr) are discussed. All structures are strongly influenced by very short Ae⋯F contacts down to circa 2.11 Å (Mg), 2.50 Å (Ca) and 2.73 Å (Sr). AIM analysis illustrates that, although Ae⋯F contacts are short, there is no bond-critical-point along this axis, indicating an essentially electrostatic interaction. The monomeric complexes feature strong C 6 F 5 ⋯C 6 F 5 π-stacking, resulting in unusually acute N F -Ae-N F angles as small as 95°. Heteroleptic (N F AeN′′) 2 complexes retain their dimeric structure in C 6 D 6 solution and there is no indication of ligand scrambling by the Schlenk equilibrium, suggesting that an electron withdrawing ligand may stabilize heteroleptic complexes. According to DFT calculations, the heteroleptic arrangement is 70 kJ mol -1 more stable than the homoleptic dimers. The Lewis acidity of MgN F 2 has been quantified with the Gutmann-Beckett method and by calculation of the Fluoride-Ion-Affinity. The latter calculations show that the Lewis acidity of MgN F 2 and CaN F 2 is comparable to that of B(C 6 F 5 ) 3 . Dimeric (MgN F 2 ) 2 fully abstracts Et 3 PO from Et 3 PO·B(C 6 F 5 ) 3 and may have potential in Lewis acid catalysis.
CRIS-Team Scopus Importer:2019-06-04

Lewis Acidic Cationic Strontium and Barium Complexes - Thum, Katharina; Martin, Johannes; Elsen, Holger; Eyselein, Jonathan; Stiegler, Lisa; Langer, Jens; Harder, Sjoerd (European Journal of Inorganic Chemistry, 2021)
Lewis acidic (BDI)Ae+ cations of the heavier metals Sr and Ba, which are not stabilized by polar solvents, have been obtained by double deprotonation of (BDI)H2+ with either SrN’’2 or BaN’’2; BDI = HC[C(Me)N(DIPP)]2, DIPP = 2,6-diisopropylphenyl, Ae = alkaline earth, N’’ = N(SiMe3)2. Due to clathrate formation [(BDI)Ae+][B(C6F5)4−] could not be crystallized, but pyrene addition gave crystalline [(BDI)Ae+ ⋅ pyrene][B(C6F5)4−] which was structurally characterized for Ae = Mg, Ca, Sr, Ba. (R2N)Ae+ cations of the heavier metals Sr and Ba were obtained by reaction of Ae(NR2)2 with [Ph3C+][B(C6F5)4−] or [PhNMe2H+][B(C6F5)4−]. Following complexes were structurally characterized: [N’’Ba+ ⋅ (tol)2][B(C6F5)4−], [N*Sr+ ⋅ PhNMe2][B(C6F5)4−], [N*Ba+ ⋅ tol][B(C6F5)4−] and [N*Ba+ ⋅ C6H6][B(C6F5)4−]; tol = toluene and N* = N(SiiPr3)2. DFT calculations show that Sr⋅⋅⋅PhNMe2 coordination is preferred over Sr⋅⋅⋅toluene bonding. The (R2N)Ae+ cations can be used as Brønsted bases (reaction with (BDI)H gave (BDI)Ae+) and may be useful precursors for a variety of Lewis base-free RAe+ cations. DFT calculations, limited to monomeric model systems including B(C6F5)4− (ωB97XD/def2tzvpp//ωB97XD/def2svp), show that there is negligible electron transfer from the pyrene or toluene ligands to the Ae2+ cation. Electrostatic attraction originates from charge-induced polarization of the (Formula presented.) -electron density in the toluene and pyrene ligands.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Ab initio calculations; Arene coordination; Barium; Cations; Strontium

Ligand Effects in Calcium Catalyzed Ketone Hydroboration - Brand, Steffen; Causero, Andrea; Elsen, Holger; Pahl, Jürgen; Langer, Jens; Harder, Sjoerd (European Journal of Inorganic Chemistry, 2020)
The first “naked” (Lewis base-free) cationic Ca amidinate complex [tBuAmDIPPCa(C6H6)]+[B(C6F5)4]– was prepared in 62 % yield tBuAmDIPP = tBuC(N–DIPP)2; DIPP = 2,6-diisopropylphenyl by reaction of [tBuAmDIPPCaH]2 with [Ph3C]+[B(C6F5)4]– in chlorobenzene. The ether-free complex tBuAmDIPPCaN(SiMe3)2 was obtained by removal of diethyl ether from its ether adduct. Crystal structures show that the amidinate ligand in both complexes is N,Aryl-chelating. In this coordination mode the bulk of the amidinate ligand is comparable to that of a DIPP-substituted β-diketiminate ligand. Isomers with N,N-coordinating amidinate ligands are circa 15 kcal/mol higher in energy and this coordination mode is only present in case additional ether ligands compensate for energy loss or in case of space limitation at the metal, e.g. in homoleptic (tBuAmDIPP)2Ca. A series of four Ca amidinate complexes, tBuAmDIPPCaX, were tested in the catalytic hydroboration of ketones and aldehydes by pinacolborane (HBpin). Catalytic activities increase for X– = I– < B(C6F5)4 – < (Me3Si)2N– ≈ H–. For catalysts with unreactive anions, like I– or B(C6F5)4 –, catalyst performance increases with the Lewis acidity of the metal and a mechanism is proposed in which HBpin and ketone coordinate to the Ca2+ ion which is followed by direct hydroboration. The more active catalysts with X– = (Me3Si)2N– or H– likely operate through a mechanism which involves intermediate metal hydride (or borate) complexes.
CRIS-Team Scopus Importer:2020-05-08
Keywords: Amidinates; Calcium; Cationic complexes; Homogeneous catalysis; Hydroboration

Lithium Aluminium Hydride and Metallic Iron: A Powerful Team in Alkene and Arene Hydrogenation Catalysis - Knüpfer, Christian; Färber, Christian; Langer, Jens; Harder, Sjoerd (Angewandte Chemie International Edition, 2023)
Alkenes that normally do not react with LiAlH4 (3-hexene, cyclohexene, 1-Me-cyclohexene), can be reduced to the corresponding alkanes by a mixture of LiAlH4 and Fe0 (the iron was activated by Metal-Vapour-Synthesis). This alkene-to-alkane conversion with a stoichiometric quantity of LiAlH4/Fe0 does not need quenching with water or acids, implying that both H's originate from LiAlH4. The LiAlH4/Fe0 combination is also a remarkably potent cooperative catalyst for hydrogenation of multi-substituted alkenes and benzene or toluene. An induction period of circa two hours and the minimally required temperature of 120 °C, suggests that the actual catalyst is a combination of Fe0 and the decomposition product of LiAlH4 (LiH and Al0). A thermally pre-activated LiAlH4/Fe0 catalyst did not need an induction time and is also active at room temperature and 1 bar H2. A combination of AliBu3 and Fe0 is an even more active hydrogenation catalyst. Without pre-activation, tetra-substituted alkenes like Me2C=CMe2 and toluene could be fully hydrogenated.
CRIS-Team Scopus Importer:2023-04-07
Keywords: Aluminium; Hydrides; Hydrogenation; Iron; Sustainability

Low-Coordinate Monomeric Zinc Hydride Complexes with Encapsulating Dipyrromethene Ligands and Reactivity with B(C6F5)3 - Ballmann, Gerd; Martin, Johannes; Langer, Jens; Färber, Christian; Harder, Sjoerd (Zeitschrift für Anorganische und Allgemeine Chemie, 2019)
The dipyrromethene (DPM) ligand is the key to isolation of monomeric Zn hydride complexes with tricoordinate zinc centers. A range of RDPM ligands with various substituents in the pole position (1,9-positions) were prepared: R = tBu, adamantyl (Ad), mesityl (Mes), 2,6-diisopropylphenyl (DIPP), 2,4,6-triphenylphenyl (Mes*), or 9-anthracenyl (Anth). Reaction of the ligands with Et2Zn gave a series of (RDPM)ZnEt complexes, which were converted with I2 to the corresponding (RDPM)ZnI compounds. The latter reacted by salt metathesis with KN(iPr)HBH3 to the series of Zn hydride complexes (RDPM)ZnH. For ligands with the larger Mes* and Anth substituents, (RDPM)ZnEt was converted to (RDPM)ZnOSiPh3, which after reaction with PhSiH3 gave the hydrides. While Zn hydride complexes with R = tBu or Ad are dimeric, all complexes with aryl-substituents are monomeric. The aryl groups span a cavity around the metal, blocking dimerization and causing a high-field shift of the 1H NMR signals due to the ASIS effect. Attempted abstraction of the hydride with B(C6F5)3 led to cleavage of the B-C6F5 bond.
CRIS-Team Scopus Importer:2019-11-15
Keywords: B(C; Dipyrromethene; Hydride; Zinc

Low Valent Magnesium Chemistry with a Super Bulky β-Diketiminate Ligand - Gentner, Thomas; Rösch, Bastian; Ballmann, Gerd; Langer, Jens; Elsen, Holger; Harder, Sjoerd (Angewandte Chemie International Edition, 2019)
The steric bulk of the well-known DIPP BDI ligand (CH[C(CH 3 )N-DIPP] 2 , DIPP=2,6-diisopropylphenyl) was increased by replacing isopropyl for isopentyl groups. This very bulky DIPeP BDI ligand could not stabilize the radical species ( DIPeP BDI)Mg . : reduction of ( DIPeP BDI)MgI with Na gave ( DIPeP BDI) 2 Mg 2 with a rather long Mg-Mg bond of 3.0513(8) Å. Addition of TMEDA prior to reduction gave complex ( DIPeP BDI) 2 Mg 2 (C 6 H 6 ), which could also be obtained as its THF adduct. It is speculated that combination of a bulky spectator ligand and TMEDA prevents dimerization of the intermediate Mg I radical, which then reacts with the benzene solvent. Complex ( DIPeP BDI) 2 Mg 2 (C 6 H 6 ), which formally contains the anti-aromatic anion C 6 H 6 2− , reacted with tBuOH as a Brønsted base to 1,3- and 1,4-cyclohexadiene and with H 2 as a two electron donor to ( DIPeP BDI) 2 Mg 2 H 2 and C 6 H 6 . It also reductively cleaved the C−F bond in fluorobenzene and gave ( DIPeP BDI)MgPh, ( DIPeP BDI)MgF, and C 6 H 6 .
CRIS-Team Scopus Importer:2019-08-16
Keywords: alkaline earth metal; bulky ligand; low valence; magnesium; metal-metal bonding

Low-valent Mg(I) complexes by ball-milling - Jedrzkiewicz, Dawid; Langer, Jens; Harder, Sjoerd (Zeitschrift für Anorganische und Allgemeine Chemie, 2022)
Mechanochemistry has great potential in the syntheses of low-valent Mg(I) complexes. Magnesium iodide precursors with three different beta-diketiminate (BDI) ligands of varying bulk have been reduced with K/KI (or Na/NaCI) using the ball-mill. Depending on the steric bulk of the ligand, the raw products are intensely colored powders, indicating the presence of (BDI)Mg center dot radicals. Extraction with pentane gave (BDI)Mg-Mg-(BDI) in excellent yields. Reaction of the powder with H-2 prior to extraction gave [(BDI)MgH](2). Extraction with benzene gave (BDI)Mg(C6H6)Mg(BDI) with a dearomatized puckered benzene dianion. Ball-milling in the presence of triphenylbenzene gave a dinuclear Mg complex with a Ph3C6H3-dianion which slowly decomposed to (BDI)Mg-Mg(BDI) and Ph3C6H3.
CRIS-Team WoS Importer:2022-05-27

Magnesium-halobenzene bonding: mapping the halogen sigma-hole with a Lewis-acidic complex - Friedrich, Alexander; Pahl, Jürgen; Eyselein, Jonathan; Langer, Jens; van Eikema Hommes, Nico; Görling, Andreas; Harder, Sjoerd (Chemical Science, 2021)
Complexes of the Lewis base-free cations (MeBDI)Mg+and (tBuBDI)Mg+with Ph-X ligands (X = F, Cl, Br, I) have been studied (MeBDI = HC[C(Me)N-DIPP]2andtBuBDI = HC[C(tBu)N-DIPP]2; DIPP = 2,6-diisopropylphenyl). For the smaller β-diketiminate ligand (MeBDI) only complexes with PhF could be isolated. Heavier Ph-X ligands could not compete with bonding of Mg to the weakly coordinating anion B(C6F5)4−. For the cations with the bulkiertBuBDI ligand, the full series of halobenzene complexes was structurally characterized. Crystal structures show that the Mg⋯X-Ph angle strongly decreases with the size of X: F 139.1°, Cl 101.4°, Br 97.7°, I 95.1°. This trend, which is supported by DFT calculations, can be explained with the σ-hole which increases from F to I. Charge calculation and Atoms-In-Molecules analyses show that Mg⋯F-Ph bonding originates from electrostatic attraction between Mg2+and the very polar Cδ+-Fδ−bond. For the heavier halobenzenes, polarization of the halogen atom becomes increasingly important (Cl < Br < I). Complexation with Mg leads in all cases to significant Ph-X bond activation and elongation. This unusual coordination of halogenated species to early main group metals is therefore relevant to C-X bond breaking.
CRIS-Team Scopus Importer:2021-03-19

Mg-Mg bond polarization induced by a superbulky β-diketiminate ligand - Rösch, Bastian; Gentner, Thomas; Eyselein, Jonathan; Friedrich, Alexander; Langer, Jens; Harder, Sjoerd (Chemical Communications, 2020)
The bulk of a recently reported superbulky β-diketiminate ligand was further increased by introducing tBu substituents in the ligand backbone. Attempts to isolate free Mg radicals with this extremely bulky ligand failed. Instead, a dinuclear Mg(i) complex with one chelating and one monodentate β-diketiminate ligand was isolated. Asymmetry in metal coordination results in a polarized Mg-Mg bond.
CRIS-Team Scopus Importer:2020-10-09

Multiple-Porphyrin Functionalized Hexabenzocoronenes - Martin, Max; Lungerich, Dominik; Hampel, Frank; Langer, Jens; Ronson, Tanya K.; Jux, Norbert (Chemistry - A European Journal, 2019)
Porphyrin–hexabenzocoronene architectures serve as good model compounds to study light-harvesting systems. Herein, the synthesis of porphyrin functionalized hexa-peri-hexabenzocoronenes (HBCs), in which one or more porphyrins are covalently linked to a central HBC core, is presented. A series of hexaphenylbenzenes (HPBs) was prepared and reacted under oxidative coupling conditions. The transformation to the respective HBC derivatives worked well with mono- and tri-porphyrin-substituted HPBs. However, if more porphyrins are attached to the HPB core, Scholl oxidations are hampered or completely suppressed. Hence, a change of the synthetic strategy was necessary to first preform the HBC core, followed by the introduction of the porphyrins. All products were fully characterized, including, if possible, single-crystal XRD. UV/Vis absorption spectra of porphyrin-HBCs showed, depending on the number of porphyrins as well as with respect to the substitution pattern, variations in their spectral features with strong distortions of the porphyrins’ B-band.
CRIS-Team Scopus Importer:2019-11-19
Keywords: hexabenzocoronene; nanographene; nanostructures; porphyrinoids; Scholl oxidation

Nucleophilic Aromatic Substitution at Benzene with Powerful Strontium Hydride and Alkyl Complexes - Rösch, Bastian; Gentner, Thomas; Elsen, Holger; Fischer, Christian; Langer, Jens; Wiesinger, Michael; Harder, Sjoerd (Angewandte Chemie International Edition, 2019)
Key to the isolation of the first alkyl strontium complex was the synthesis of a strontium hydride complex that is stable towards ligand exchange reactions. This goal was achieved by using the super bulky beta-diketiminate ligand (BDI)-B-DIPeP (CH[C(Me)N-DIPeP](2), DIPeP = 2,6-diisopentylphenyl). Reaction of (BDI)-B-DIPeP-H with Sr[N(SiMe3)(2)](2) gave ((BDI)-B-DIPeP)SrN(SiMe3)(3) which was converted with PhSiH3 into [((BDI)-B-DIPeP)SrH2]. Dissolved in C6D6, the strontium hydride complex is stable up to 70 degrees C At 60 degrees C, H-D isotope exchange gave full conversion into ([(BDI)-B-DIPeP)SrD](2) and C6D5H. Since H-D exchange with D-2 is facile, the strontium hydride complex served as a catalyst for the deuteration of C6H6 by D-2. Reaction of [( (BDI)-B-DIPeP)SrH](2) with ethylene gave [( (BDI)-B-DIPeP)SrEt](2). The high reactivity of this alkyl strontium complex is demonstrated by facile ethylene polymerization and nucleophilic aromatic substitution with C6D6, giving alkylated aromatic products and [((BDI)-B-DIPeP)SrD](2).
CRIS-Team WoS Importer:2019-04-23

On the existence of low-valent magnesium-calcium complexes - Mai, Jonathan; Rösch, Bastian; Patel, Neha; Langer, Jens; Harder, Sjoerd (Chemical Science, 2023)
DFT-Calculations predict that a low-valent complex (BDI)Mg-Ca(BDI) with bulky beta-diketiminate (BDI) ligands is thermodynamically stable. It was attempted to isolate such a complex by salt-metathesis between [((BDI)-B-DIPeP*) Mg-Na+](2) and [((BDI)-B-DIPeP)CaI](2) ((BDI)-B-DIPeP = HC[C(Me)N-DIPeP](2); (BDI)-B-DIPeP* = HC [C(tBu)N-DIPeP](2); DIPeP = 2,6-CH(Et)(2)-phenyl). Whereas in alkane solvents no reaction was observed, salt-metathesis in C6H6 led to immediate C-H activation of benzene to give ((BDI)-B-DIPeP*) MgPh and ((BDI)-B-DIPeP) CaH, the latter crystallizing as a THF-solvated dimer [((BDI)-B-DIPeP) CaHTHF](2). Calculations suggest reduction and insertion of benzene in the Mg-Ca bond. The activation enthalpy for the subsequent decomposition of C(6)H(6)2(-) into Ph- and H- is only 14.4 kcal mol(-1). Repeating this reaction in the presence of naphthalene or anthracene led to heterobimetallic complexes in which naphthalene(2-) or anthracene(2-) anions are sandwiched between ((BDI)-B-DIPeP*)Mg+ and ((BDI)-B-DIPeP)Ca+ cations. These complexes slowly decompose to their homometallic counterparts and further decomposition products. Complexes in which naphthalene(2-) or anthracene(2-) anions are sandwiched between two ((BDI)-B-DIPeP)Ca+ cations were isolated. The low-valent complex (BDI)-B-(DIPeP*)Mg-Ca((BDI)-B-DIPeP) could not be isolated due to its high reactivity. There is, however, strong evidence that this heterobimetallic compound is a fleeting intermediate.
CRIS-Team WoS Importer:2023-05-26

Opportunities with calcium Grignard reagents and other heavy alkaline-earth organometallics - Harder, Sjoerd; Langer, Jens (Nature Reviews Chemistry, 2023)
More than a century old, magnesium Grignard reagents remain essential to the toolbox of organic chemists. Although similar reagents with the neighbouring group 2 metal Ca have been explored, the considerably higher polarity and reactivity of the Ca–C bond result in undesired decomposition pathways. Ca Grignard reagents have found academic interest but have never fully developed into an established synthetic tool. Recent research activities, however, provide facile access to these highly reactive organocalcium species, including in situ preparation and ball milling approaches to tackle the challenge of controlling their extreme sensitivity. Heavier Grignard reagents are not just more reactive but profit from unique chemical transformations. Insight into the transition metal-like properties of Ca, Sr and Ba is only just emerging. Considering the rapidly developing field of alkaline-earth metal-mediated catalysis, heavy Grignard reagents will probably have a bright future. [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2023-11-17

Oxygen-rich tetrahedral surface phase on high-temperature rutile VO2(110)(T) single crystals - Wagner, Margareta; Planer, Jakub; Heller, Bettina; Langer, Jens; Limbeck, Andreas; Boatner, Lynn A.; Steinrück, Hans-Peter; Redinger, Josef; Maier, Florian; Mittendorfer, Florian; Schmid, Michael; Diebold, Ulrike (Physical Review Materials, 2021)
Vanadium dioxide undergoes a metal-insulator transition from an insulating (monoclinic) to a metallic (tetragonal) phase close to room temperature, which makes it a promising functional material for many applications, e.g., as chemical sensors. Not much is known about its surface and interface properties, although these are critical in many applications. In this paper, we present an atomic-scale investigation of the tetragonal rutile VO2(110)(T) single-crystal surface and report results obtained with scanning tunneling microscopy, low-energy electron diffraction, and x-ray photoelectron spectroscopy, supported by density-functional-theory-based calculations. The surface reconstructs into an oxygen-rich (2 x 2) superstructure that coexists with small patches of the underlying unreconstructed (110)-(1 x 1) surface when the crystal is annealed >600 degrees C. The best structural model for the (2 x 2) surface termination, conceptually derived from a vanadium pentoxide (001) monolayer, consists of rings of corner-shared tetrahedra. Over a wide range of oxygen chemical potentials, this reconstruction is more stable than the unreconstructed (110) surface and models proposed in the literature.
CRIS-Team WoS Importer:2021-12-17

Porphyrin-Hexaphenylbenzene Conjugates via Mixed Cyclotrimerization Reactions - Martin, Max; Dill, Maximilian; Langer, Jens; Jux, Norbert (Journal of Organic Chemistry, 2019)
Mixed cyclotrimerization reactions of diarylacetylenes (tolans) were applied to generate a library of multiple porphyrin-hexaphenylbenzene (HPB) architectures. Successful reactions, which could be influenced by the ratio of tolan starting materials, were conducted using dicobaltoctacarbonyl as a catalyst. Separation of the reaction products was performed by chromatographic and crystallization techniques. The physical properties were investigated with respect to the number of porphyrins per HPB and their substitution pattern.
CRIS-Team WoS Importer:2019-02-21

Redox-active inverse crowns for small molecule activation - Maurer, Johannes; Klerner, Lukas; Mai, Jonathan; Stecher, Hannah; Thum, Stefan; Morasch, Michael; Langer, Jens; Harder, Sjoerd (Nature Chemistry, 2025)
Cyclic crown ethers bind metal cations to form host–guest complexes. Lesser-known inverse crowns are rings of metal cations that encapsulate anionic entities, enabling multiple deprotonation reactions, often with unusual selectivity. Self-assembly of a cycle of metal cations around the multiply charged carbanion during the deprotonation reaction is the driving force for this reactivity. Here we report the synthesis of a pre-assembled inverse crown featuring Na+ cations and a redox-active Mg0 centre. Reduction of N2O followed by N2 release and subsequent encapsulation of O2− demonstrates its reduce-and-capture functionality. Calculations reveal that this essentially barrier-free process involves a rare N2O2− dianion, embedded in the metalla-cycle. The inverse crown can adapt itself for binding larger anions like N2O22− through a self-reorganization process involving ring expansion. The redox-active inverse crown combines the advantages of a strong reducing agent with anion stabilizing properties provided by the ring of metal cations, leading to high reactivity and selectivity. (Figure presented.)
CRIS-Team Scopus Importer:2025-02-28

Retro-Diels-Alder decomposition of norbornadiene mediated by a cationic magnesium complex - Thum, Katharina; Pahl, Jürgen; Eyselein, Jonathan; Elsen, Holger; Langer, Jens; Harder, Sjoerd (Chemical Communications, 2021)
First evidence for the coordination of norbornadiene (nbd) and dicyclopentadiene (dcpd) with the main group metal Mg is provided by the crystal structures of adducts with cationic beta-diketiminate (BDI) Mg complexes. While the dcpd complex is thermally stable, [(BDI)Mg+center dot nbd][B(C6F5)(4)(-)] shows slow room temperature retro-Diels-Alder decomposition to give a complex with the cation (BDI)Mg(C5H5)Mg(BDI)(+).
CRIS-Team WoS Importer:2021-05-28

s-Block metal complexes of superbulky (tBu3Si)2N-: a new weakly coordinating anion? - Knüpfer, Christian; Klerner, Lukas; Mai, Jonathan; Langer, Jens; Harder, Sjoerd (Chemical Science, 2024)
Sterically hindered amide anions have found widespread application as deprotonation agents or as ligands to stabilize metals in unusual coordination geometries or oxidation states. The use of bulky amides has also been advantageous in catalyst design. Herein we present s-block metal chemistry with one of the bulkiest known amide ligands: (tBu3Si)2N- (abbreviated: tBuN-). The parent amine (tBuNH), introduced earlier by Wiberg, is extremely resistant to deprotonation (even with nBuLi/KOtBu superbases) but can be deprotonated slowly with a blue Cs+/e- electride formed by addition of Cs0 to THF. (tBuN)Cs crystallized as a separated ion-pair, even without cocrystallized solvent. As salt-metathesis reactions with (tBuN)Cs are sluggish and incomplete, it has only limited use as an amide transfer reagent. However, ball-milling with LiI led to quantitative formation of (tBuN)Li and CsI. Structural characterization shows that (tBuN)Li is a monomeric contact ion-pair with a relatively short N-Li bond, an unusual T-shaped coordination geometry around N and extremely short Li?Me anagostic interactions. Crystal structures are compared with Li and Cs complexes of less bulky amide ligands (iPr3Si)2N- (iPrN-) and (Me3Si)2N- (MeN-). DFT calculations show trends in the geometries and electron distributions of amide ligands of increasing steric bulk (MeN- < iPrN- < tBuN-) and confirm that tBuN- is a rare example of a halogen-free weakly coordinating anion.
CRIS-Team Scopus Importer:2024-03-15

s-Block Metal-Lanthanide Bonding: Direct Comparison of Mg-Yb and Mg-Ca Complexes - Thakur, Sandeep Kumar; Roig, Nil; Maurer, Johannes; Langer, Jens; Alonso, Mercedes; Harder, Sjoerd (Journal of the American Chemical Society, 2025)
Despite considerable progress in understanding the fundamental aspects of metal-metal bonding, lanthanide-metal bonding is limited to interactions between lanthanide (Ln) metals and electron-rich p- or d-block metals. Exemplified by a Mg-Yb complex, we present synthesis and extensive computational analyses of the first s-block metal-Ln bond. Key to its formation is the unique Mg0 complex [(BDI*)MgNa]2 (1) which can be viewed as a dimer consisting of two magnesyl anions, (BDI*)Mg-, bridged by two Na+ cations (BDI* = HC[C(tBu)N-DIPeP]2, DIPeP = 2,6-CHEt2-phenyl). Reaction of dimeric 1 with (YbN’’2)2 (N’’ = N(SiMe3)2) quantitatively gave the mixed complex [(BDI*)MgNa/YbN’’2] (2-Yb) in which (BDI*)Mg- anions bridge between Yb2+ and Na+ cations (Mg-Yb: 3.466(1), Mg-Na: 3.415(1) Å). Atoms-In-Molecules shows Mg-Yb and Mg-Na bond paths corresponding to weak electrostatic interactions. Complex 2-Yb is isostructural to previously reported [(BDI*)MgNa/CaN’’2] (2-Ca). Weak Mg0-M2+ (M = Ca, Yb) bonding is supported by facile exchange reactions with (SrN’’2)2 leading to formation of [(BDI*)MgNa/SrN’’2] (2-Sr). Energy decomposition analysis (EDA-NOCV) confirmed major electrostatic Mg0-M2+ bonding (63-66%), while orbital interactions are less significant (19-20%). Both, 2-Ca and 2-Yb show considerable Mg0 → M2+ electron transfer leading to oxidation-state ambiguities (Mg0-M+II ↔ Mg+I-M+I). Effective-Oxidation-State calculations assign the following metal oxidation states, Na+I-Mg0-M+II, with a reliability index of 69-72%. Despite structural and electronic similarities, there are differences in reactivities. Complex 2-Ca reacts only as a 2-electron reducing agent whereas 2-Yb can deliver up to three electrons. This study includes reactions with N2O, TEMPO, and Me3PX (X = O, S, Se). While only 2-Ca could be converted in a complex with incorporated O2-, complexes with S2- or Se2- have been isolated for both.
CRIS-Team Scopus Importer:2025-04-18

Selectivity control in the reactivity of dipyrromethene gallium(I) complexes - Richter, Tim; Thum, Stefan; Townrow, Oliver; Langer, Jens; Wiesinger, Michael; Harder, Sjoerd (Journal of Organometallic Chemistry, 2024)
Following the recent isolation and structural characterization of the first low-valent GaI complex with a monoanionic dipyrromethenide ligand (DPM), herein (DPM)GaI complexes with bulky aryl-substituents in the 1- and 9-positions are described. This study focusses on three DPM ligands with mesityl substituents (MesDPM), 2,6-diisopropylphenyl substituents (DIPPDPM), or 10-isopropyl-9-anthracenyl substituents (iPr-AnthDPM); the synthesis to the latter unknown ligand is described. The precursors (RDPM)GaI2 were obtained by reaction of the corresponding alkali metal complexes (RDPM)M (M = Na or K) with GaI3 and characterized by X-ray diffraction. Crystal structures show the efficient shielding of the GaI2 unit by two flanking aryl groups. In a subsequent reduction step, (DIPPDPM)GaI and (iPr-AnthDPM)GaI have been isolated. Comparison of the crystal structure of (DIPPDPM)GaI with that of a similar β-diketiminate GaI complex shows that the Ga center in the DPM complex is well shielded by flanking DIPP substituents. Despite this favorable ligand geometry, isolation of the corresponding (DPM)Ga=N(SiMe3) complexes failed due to further reaction with a second equivalent of Me3SiN3. This resulted in clean formation of the tetrazagallole complex (tBuDPM)Ga[N4(SiMe3)2] and the amide/azide combination (iPr-AnthDPM)Ga(N3)N(SiMe3)2, both structurally characterized by X-ray diffraction. Selective formation of both complexes shows that the substituents in the DPM ligand effectively control the course of the reaction. DFT calculations show that independent of the substituent (tBu, DIPP, or iPr-Anth) the amide/azide combination is always circa 20 kcal/mol more stable than the tetrazagallole product. The latter must therefore be formed by kinetic control.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Azide; Dipyrromethene ligand; Gallium; Imido; Low-valent

Similarities and Differences in Benzene Reduction with Ca, Sr, Yb and Sm: Strong Evidence for Tetra-Anionic Benzene - Thakur, Sandeep Kumar; Roig, Nil; Monreal-Corona, Roger; Langer, Jens; Alonso, Mercedes; Harder, Sjoerd (Angewandte Chemie International Edition, 2024)
Inverse sandwich complexes of Yb and Sm stabilized by a bulky β-diketiminate (BDI) ligand have been prepared: (BDI)Ln(η6,η6-C6H6)Ln(BDI); Ln=lanthanide. Coordinated benzene ligands can be neutral, di-anionic or, often controversially discussed, even tetra-anionic. The formal charge on benzene is correlated to assignment of the metal oxidation state which generally poses a problem. Herein, we take advantage of the structural similarities found when comparing CaII with YbII, and SrII with SmII complexes. In this work, we found an excellent overlap of the Ca/Yb inverse sandwich structures but a striking difference for the Sr/Sm pair. The much shorter Sm−N and Sm-C6H6 distances are strong evidence for a SmIII-benzene−4-SmIII assignment. This was further supported by NMR spectroscopy, magnetic susceptibility, reactivity and comprehensive computational investigation.
CRIS-Team Scopus Importer:2024-05-24
Keywords: Aromaticity; Benzene; Reduction; Samarium; Ytterbium

Strongly reducing magnesium(0) complexes - Rösch, Bastian; Gentner, Thomas; Eyselein, Jonathan; Langer, Jens; Elsen, Holger; Harder, Sjoerd (Nature, 2021)
A complex of a metal in its zero oxidation state can be considered a stabilized, but highly reactive, form of a single metal atom. Such complexes are common for the more noble transition metals. Although rare examples are known for electronegative late-main-group p-block metals or semimetals1-6, it is a challenge to isolate early-main-group s-block metals in their zero oxidation state7-11. This is directly related to their very low electronegativity and strong tendency to oxidize. Here we present examples of zero-oxidation-state magnesium (that is, magnesium(0)) complexes that are stabilized by superbulky, monoanionic, β-diketiminate ligands. Whereas the reactivity of an organomagnesium compound is typically defined by the nucleophilicity of its organic groups and the electrophilicity of Mg2+ cations, the Mg0 complexes reported here feature electron-rich Mg centres that are nucleophilic and strongly reducing. The latter property is exemplified by the ability to reduce Na+ to Na0. We also present a complex with a linear Mg3 core that formally could be described as a MgI-Mg0-MgI unit. Such multinuclear mixed-valence Mgn clusters are discussed as fleeting intermediates during the early stages of Grignard reagent formation. Their remarkably strong reducing power implies a rich reactivity and application as specialized reducing agents.
CRIS-Team Scopus Importer:2021-05-14

Switching between inner- and outer-sphere PCET mechanisms of small-molecule activation: Superoxide dismutation and oxygen/superoxide reduction reactivity deriving from the same manganese complex - Kenkel, Isabell; Franke, Alicja; Dürr, Maximilian; Zahl, Achim; Dücker-Benfer, Carlos; Langer, Jens; Filipovic, Milos; Yu, Meng; Puchta, Ralph; Fiedler, Stephanie R.; Shores, Matthew P.; Goldsmith, Christian R.; et al. (Journal of the American Chemical Society, 2017)

Synthesis of Superbulky Amide Ligands by Addition of Polar Reagents to Sila–Imine - Knüpfer, Christian; Klerner, Lukas; Raucheisen, Michael; Langer, Jens; Harder, Sjoerd (Chemistry - A European Journal, 2024)
The chemistry of extremely bulky amide ligands is troubled by difficulties in deprotonation of the parent amine. As an alternative route to superbulky amide reagents, the addition of polar reagents to a sila–imine has been investigated. Attempts to synthesize the superbulky amide anion (tBu3Si)2N− by addition of tBuLi to tBu2Si=N(SitBu3) failed and gave tBu3Si(tBu2HSi)NLi and isobutene. Reaction of the sila–imine with KOtBu successfully led to tBu3Si[tBu2(tBuO)Si]NK which crystallized as a separated ion–pair. Reaction with the slightly bulkier KOAd (Ad=1-adamantyl) led in presence of THF to ether ring–opening. Reaction with tBuOH gave tBu3Si[tBu2(tBuO)Si]NH but this amine cannot be easily deprotonated. Reaction with (BDI*)MgnBu in presence of THF gave (BDI*)Mg+ ⋅ (THF)2 and the non–coordinating anion tBu3Si[tBu2(nBu)Si]N−; BDI*=ß-diketiminate ligand HC[C(tBu)N−DIPP]2, DIPP=2,6-diisopropylphenyl. Reaction of Mg(nBu)2 with tBu2Si=N(SitBu3) led to a Mg complex with one amide ligand: tBu3Si[tBu2(nBu)Si]N−. The other superbulky amide anion isomerized by internal deprotonation of a tBu-substituent to give a primary carbanion that is also coordinated to Mg. Although the amide–to–carbanion isomerization is highly contrathermodynamic, it allows for coordination of both anions to a single Mg center. The new bulky amides are rare cases of halogen–free weakly coordinating anions.
CRIS-Team Scopus Importer:2024-04-19
Keywords: Amide ligands; bulky ligands; s-block metals; weakly coordinating anion

Synthesis, Structure, and Reactivity of a Superbulky Low-Valent β-Diketiminate Al(I) Complex - Grams, Samuel; Mai, Jonathan; Langer, Jens; Harder, Sjoerd (Organometallics, 2022)
Low-valent β-diketiminate Al(I) complexes are generally synthesized in low yields (<20%). This is due to an intermolecular decomposition reaction. A new β-diketiminate Al(I) complex with a very bulky β-diketiminate ligand DIPePBDI was obtained in a high yield (81%) and the raw product was found to be essentially pure (DIPePBDI = HC[C(Me)N(DIPeP)]2; DIPeP = 2,6-C(H)Et2-phenyl). The crystal structure of (DIPePBDI)Al shows a monomeric complex. The reaction of (DIPePBDI)Al with AlBr3 gave (DIPePBDI)AlBr2 and Al(0). The reaction of (DIPePBDI)Al with KCH(SiMe3)2 led to deprotonation of a backbone Me group and formation of a K aluminyl complex. A minor side-product in which the BDI ligand was cleaved is also described. The very high yield of (DIPePBDI)Al makes it a welcome addition to the family of β-diketiminate Al(I) complexes.
CRIS-Team Scopus Importer:2022-10-28

Synthesis, Structure, and Reactivity of a Superbulky low-Valent β-diketiminate Ga(I) Complex - Richter, Tim; Thum, Stefan; Townrow, Oliver; Wiesinger, Michael; Langer, Jens; Harder, Sjoerd (Zeitschrift für Anorganische und Allgemeine Chemie, 2024)
A low-valent GaI complex with the superbulky β-diketiminate ligand DIPePBDI (HC[C(Me)N−DIPeP]2, DIPeP=2,6-C(H)Et2-phenyl)) was obtained by reduction of (DIPePBDI)GaI2 (1) with KC8 in toluene. Considering that (BDI)GaI and analogue (BDI)AlI complexes are prone to decomposition and can generally only be obtained in low yields (20–40 %), the quantitative formation of (DIPePBDI)GaI (2) is remarkable and no doubt related to its excellent thermal stability even in refluxing toluene. Although the low-valent metal center in 2 is sterically protected by the superbulky DIPePBDI ligand, it is readily oxidized by N2O to give intermediate (DIPePBDI)Ga=O which readily decomposed by abstracting a proton from the backbone Me-substituent. Reaction with trimethylsilyl azide gave an intermediate imido complex (DIPePBDI)Ga=N(SiMe3)2 which reacted with a second equivalent of Me3SiN3 to a mixture of an azide/amido complex (DIPePBDI)GaN3[N(SiMe3)2] (4) and a tetrazagallole complex (DIPePBDI)Ga[N4(SiMe3)2] (5) in a 1 : 2 ratio. Whereas the azide/amido complex 4 could be structurally characterised, the tetraazagallole complex 5 was identified by NMR spectroscopy. DFT calculations on (DIPePBDI)GaI (2) and its reaction products complement this study.
CRIS-Team Scopus Importer:2024-06-07
Keywords: bulky; Gallium; Low-valent; β-diketiminate

Trapping of soluble, KCl-stabilized Cu(i) hydrides with CO2 gives crystalline formates - Grasruck, Alexander; Parla, Giorgio; Lou, Lisha; Langer, Jens; Neiß, Christian; Herrera, Alberto; Frieß, Sibylle; Görling, Andreas; Schmid, Günter; Dorta, Romano (Chemical Communications, 2023)
Cu(i)-Hydrido complexes supported by dibenzo[b,f]azepinyl P-alkene hybrid ligands and stabilized by electrostatic interactions in a Cu-H⋯KCl⋯BR3 arrangement can be trapped with CO2 at low temperature to afford Cu(i)-formates. The complexes are isolable with and without a pendant BEt3 group and show strong Cu-O and weak B-O interactions.
CRIS-Team Scopus Importer:2023-12-15

Tuning the selectivity of P4 reduction at alkaline-earth metal centres - Thum, Stefan; Townrow, Oliver; Langer, Jens; Harder, Sjoerd (Chemical Science, 2025)
Reduction of P4 with β-diketiminate MgI complexes, (BDI)MgMg(BDI), depends strongly on the bulk of the ligand. Whereas superbulky BDI ligands gave selective reduction to P42− in a butterfly conformation, reduction with a less bulky ligand gave various products among which P84− had a realgar-type structure. The selectivity of P4 reduction can also be controlled by metal choice. Reduction of P4 with CaI synthons of general type (BDI*)Ca-X-Ca(BDI*) in which BDI* is a superbulky ligand and X is a bridging dianion (C6H62− < p-xylene2− < N22−) led to reduction of P4 to the very common, stable Zintl anion P73−. Monitoring this process with 31P NMR shows that cyclo-P42− is an intermediate en route to P73−. Conversion rates increase with increasing reducing power: X = C6H62− < p-xylene2− < N22−. A complex with the weakly reducing DBA2− dianion led to selective P4 reduction to cyclo-P42− (DBA = 9,10-dimethyl-diboraanthracene). DBA inhibits P4-to-P7 conversion, most likely by capturing the electron needed for further P4 reduction by radical processes. Experimental investigations are supported by crystal structure determinations and a computational DFT study which also shows that the nature of metal-P4 bonding (covalent or ionic) determines the preference for formation of butterfly-shaped P42− or planar 6π-electron aromatic cyclo-P42−
CRIS-Team Scopus Importer:2025-02-17

Unsupported Mg-Alkene Bonding - Thum, Katharina; Friedrich, Alexander; Pahl, Jürgen; Elsen, Holger; Langer, Jens; Harder, Sjoerd (Chemistry - A European Journal, 2020)
The first intermolecular early main group metal-alkene complexes were isolated. This was enabled by using highly Lewis acidic Mg centers in the Lewis base-free cations ((BDI)-B-Me)Mg+ and ((BDI)-B-tBu)Mg+ with B(C6F5)(4)(-) counterions ((BDI)-B-Me=CH[C(CH3)N(DIPP)](2), (BDI)-B-tBu=CH[C(tBu)N(DIPP)](2), DIPP=2,6-diisopropylphenyl). Coordination complexes with various mono- and bis-alkene ligands, typically used in transition metal chemistry, were structurally characterized for 1,3-divinyltetramethyldisiloxane, 1,5-cyclooctadiene, cyclooctene, 1,3,5-cycloheptatriene, 2,3-dimethylbuta-1,3-diene, and 2-ethyl-1-butene. In all cases, asymmetric Mg-alkene bonding with a short and a long Mg-C bond is observed. This asymmetry is most extreme for Mg-(H2C=CEt2) bonding. In bromobenzene solution, the Mg-alkene complexes are either dissociated or in a dissociation equilibrium. A DFT study and AIM analysis showed that the C=C bonds hardly change on coordination and there is very little alkene -> Mg electron transfer. The Mg-alkene bonds are mainly electrostatic and should be described as Mg2+ ion-induced dipole interactions.
CRIS-Team WoS Importer:2021-01-15

Zinc complexes of chloroquine and hydroxychloroquine versus the mixtures of their components: Structures, solution equilibria/speciation and cellular zinc uptake - Squarcina, Andrea; Franke, Alicja; Senft, Laura; Onderka, Constantin; Langer, Jens; Vignane, Thibaut; Filipovic, Milos R.; Grill, Peter; Michalke, Bernhard; Ivanović-Burmazović, Ivana (Journal of Inorganic Biochemistry, 2024)
The zinc complexes of chloroquine (CQ; [Zn(CQH+)Cl3]) and hydroxychloroquine (HO-CQ; [Zn(HO-CQH+)Cl3]) were synthesized and characterized by X-Ray structure analysis, FT-IR, NMR, UV–Vis spectroscopy, and cryo-spray mass spectrometry in solid state as well as in aqueous and organic solvent solutions, respectively. In acetonitrile, up to two Zn2+ ions bind to CQ and HO-CQ through the tertiary amine and aromatic nitrogen atoms (KN-aminCQ = (3.8 ± 0.5) x 104 M−1 and KN-aromCQ = (9.0 ± 0.7) x 103 M−1 for CQ, and KN-aminHO-CQ = (3.3 ± 0.4) x 104 M−1 and KN-aromHO-CQ = (1.6 ± 0.2) x 103 M−1 for HO-CQ). In MOPS buffer (pH 7.4) the coordination proceeds through the partially deprotonated aromatic nitrogen, with the corresponding equilibrium constants of KN-arom(aq)CQ = (3.9 ± 1.9) x 103 M−1and KN-arom(aq)HO-CQ = (0.7 + 0.4) x 103 M−1 for CQ and HO-CQ, respectively. An apparent partition coefficient of 0.22 was found for [Zn(CQH+)Cl3]. Mouse embryonic fibroblast (MEF) cells were treated with pre-synthesized [Zn((HO-)CQH+)Cl3] complexes and corresponding ZnCl2/(HO-)CQ mixtures and zinc uptake was determined by application of the fluorescence probe and ICP-OES measurements. Administration of pre-synthesized complexes led to higher total zinc levels than those obtained upon administration of the related zinc/(hydroxy)chloroquine mixtures. The differences in the zinc uptake between these two types of formulations were discussed in terms of different speciation and character of the complexes. The obtained results suggest that intact zinc complexes may exhibit biological effects distinct from that of the related zinc/ligand mixtures.
CRIS-Team Scopus Importer:2024-01-26
Keywords: Chloroquine; Ionophore; Solution equilibria; Zinc; Zinc uptake